A method for preparing thermoplastic polyvinyl alcohol derivatives by molten state reaction and its products
By performing the reaction product generated by the ester bond condensation reaction in the melting state as a primer layer, the problem of expensive platinum catalyst and unreacted substance migration of silicone-based compositions in catalytic hydrosilicification reaction is solved, and the anchoring and fluidity are improved , suitable for high-speed labeling applications.
Patent Information
- Application Number
- CN201980094532.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-03-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2039-03-18
AI Technical Summary
When used in catalytic hydrogenation of silicone-based compositions of existing release liners, the expensive platinum catalyst and the unreacted crosslinking agent compounds are prone to migrating, resulting in printing quality problems and insufficient anchoring properties, especially in high-speed labeling applications. Stable anchoring.
The ester bond formed in a molten state is used to form a condensation reaction to form a reaction product containing a carboxylic acid residue and a thermoplastic polyvinyl alcohol derivative as a primer layer of a paper substrate, which is used to improve the anchoring properties of the silicone-based composition and Fluidity, reduce dependence on platinum catalysts.
The anchoring and fluidity of the silicone-based composition is improved, the amount of platinum catalyst is reduced, the stability and printing quality of high-speed labeling applications are enhanced, the migration of unreacted substances is reduced, and the production cost is reduced.
Smart Images

Figure CN113993910B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a composition for a release liner substrate and a product thereof. The present invention also relates to a method for manufacturing a composition and a product thereof, wherein the composition is suitable for a primer layer of a release liner substrate capable of bonding silicone in a catalytic hydrosilation reaction. Background Art
[0002] As disclosed herein, release liner refers to an industrially manufactured paper substrate that has been calendered and coated with a silicone-based composition (i.e., release coating), which is subsequently thermally cured in a catalytic hydrosilation reaction. The combination of an industrially manufactured cellulose fiber-based support layer and a primer layer is referred to as a paper substrate. The combination of a paper substrate and a cured silicone-based release layer is referred to as a release liner. Catalytic hydrosilation, also known as hydrosilylation, refers to the formation of a covalent bond between a functional vinyl group in a silicone-based polymer and a hydride silicon (Si-H) group in a crosslinker compound in the presence of a platinum catalyst. The reaction produces a solid release layer on the surface of the paper substrate. The solid release layer has a dehesive property. Therefore, for example, a release liner can be used to shield the pressure-sensitive adhesive layer of a label, which is intended to adhere to the surface of an object. Release liner is widely used as a non-blocking backing material for self-adhesive products (e.g., self-adhesive labels).
[0003] The release liner as disclosed herein comprises a calendered cellulose fiber-based support layer. The calendered cellulose fiber-based support layer can be used to provide a dimensionally stable and dense surface to which the release coating can be applied. A typical cellulose fiber-based support layer suitable for use on the release liner is a calendered industrial paper. Industrial paper is usually made from chemical pulp, for example, bleached sulfate pulp (Kraft pulp). Examples of industrially manufactured papers that can be used in the production of release liners are: glass paper, super calendered kraft (SCK) paper and clay coated kraft (CCK) paper.
[0004] Release coatings are usually silicone-based compositions, which are applied to a paper substrate in the form of an oil, and then the release coating is cured to form a release layer. Release coatings based on silicone compounds are usually easy to apply and have good fluidity. Among various thermal curing methods, low temperature curing (abbreviated as LTC) is an energy-saving and advantageous method. Low temperature curing herein refers to a catalytic hydrosilation reaction that occurs at a temperature below 120°C, preferably at 55°C to 110°C. Release coatings based on silicone compounds are expensive. The platinum catalyst used to complete the catalytic hydrosilation reaction is very expensive. Due to the high cost, efforts have been made to reduce the amount of silicone compounds and platinum required to provide a release layer. Typically, in order to obtain a well-cured silicone network, a crosslinker compound is used in an amount exceeding the stoichiometric amount to ensure complete curing of the base polymer. Due to the oily nature of the uncured crosslinker compound, at least some of the unreacted crosslinker compounds may migrate in the paper substrate, so this excess amount causes problems for the wound label laminate web during storage. Industrially manufactured paper substrates are never completely closed or impermeable and may contain some openings or pores, thereby allowing uncured crosslinker compounds to penetrate the paper substrate and reach the other side of the release liner, thereby contaminating the adjacent surface of the label laminate web on the roll. When in contact with the label laminate web, the uncured crosslinker compound can smear part of the cover material surface and cause printing quality problems, such as poor print quality control or uneven printed surface strength, especially when the cover material is a film cover substrate (e.g., polyethylene, polypropylene, polyethylene terephthalate or similar widely used synthetic thermoplastic polymers).
[0005] The paper substrate generally includes a primer layer, which can be used to improve the performance of the paper substrate. The paper substrate surface is preferably configured to be compatible with subsequent release coatings and thermal curing processes. Polyvinyl alcohol (PVA) is a synthetic polymer with excellent film-forming, emulsifying and adhesive properties. It is also relatively resistant to oils and greases. It has high tensile strength and flexibility, as well as low air permeability. These properties can be used to provide a layer with a barrier effect, for example, by coating the surface of a cellulose fiber-based support layer with a primer layer comprising PVA. The primer layer is generally located in a release liner between a cellulose fiber-based support layer and a silicone-based release layer. The barrier layer improves the compactness and smoothness of the paper surface. The barrier layer also helps prevent the uncured silicone of the release layer from migrating to the cellulose fiber-based support layer.
[0006] While the primer layer may provide some barrier effect, unreacted crosslinker has been observed to migrate through the primer layer to the other side of the paper substrate beneath the primer layer despite the presence of a film-forming primer layer. Industrially manufactured paper substrates are never completely closed or impermeable and may contain some openings or pores, thereby allowing uncured crosslinker compounds to penetrate the paper substrate and reach the other side of the release liner, thereby contaminating the adjacent surface of the label laminate web on the reel.
[0007] In addition to the migration phenomenon disclosed above, another problem associated with current release liners is the relatively low anchoring of the release layer to the paper substrate. As label processing develops, the speed of the coating machine used to apply the release coating has increased significantly. It is necessary to optimize the reaction temperature during the addition cure reaction of the release coating containing silicone polymers and reduce the reaction time to improve the cost efficiency of the coating process. The new fast-curing silicones can have a highly branched molecular structure, which is more branched than the molecular structures of previous generations. The branched molecular structure leads to faster reaction kinetics. Therefore, the new fast-curing silicones require less time for the addition cure reaction.
[0008] When the amount of platinum catalyst is reduced from the current level of 50 to 35 ppm to a lower level, for example, to 30 ppm or lower, or even as low as 10 ppm, problems associated with anchoring of silicone compounds may occur. However, the reduction in the amount of platinum catalyst and the curing time of silicone should not adversely affect the relative peeling value (rub-off value) of the release layer, because the release layer may be stored for a period of time before use, so the relative peeling value should remain consistent over time. This places a demand on the paper substrate, which should promote the long-term stable anchoring of silicone on the paper substrate at low platinum levels, while being able to use fast-curing silicone compounds, which is conducive to reducing the high-speed release value (high-speed release value). The stable anchoring of the release layer is particularly important in high-speed labeling applications. Modern labeling processes may have very high speeds, which challenges the release properties of the release liner, which did not exist in the past. Therefore, it is important that the release layer is firmly anchored to the paper substrate so that the release liner can be used as a reliable debonding platform in high-speed applications. The release value is used to represent the minimum amount of force required to separate the label or excess matrix material from the release liner. Modern high-speed labeling applications can run at very high speeds (up to tens of thousands of labels dispensed per hour), which requires a release liner with a sufficiently low and stable high-speed release value so that the dispensing of labels from the release liner can proceed without interruption. The higher the speed of the labeling process, the smaller the acceptable amount of defects in the anchoring level of the release layer to the paper substrate. This requirement is increased due to the reduction in the basis weight (grams) of the paper used in high-speed release liner applications, and the basis weight (grams) in the paper substrate and the outer material (which may also be paper) will also be reduced. Therefore, the reduction in basis weight also produces a lighter label laminate web and a subsequent weaker excess matrix material, which needs to be peeled off from the release liner with less force than before to avoid damaging the matrix material. The optimal anchoring level is also reflected in cost savings, because a lighter label laminate web corresponds to a thinner outer material. Therefore, the amount of labels produced by the same amount of outer material can be increased.
[0009] Existing methods for improving the anchoring of release layers to paper substrates have focused on paper substrates to which organic molecules have been grafted or methods of producing modified polymers containing vinyl groups through solvent-based reactions, either organic solvents or water.
[0010] Publication WO 2005 / 071161 discloses a method for grafting organic molecules onto the surface of a cellulose support. Petroleum ether is mentioned as a grafting solvent for the reaction on the paper surface. Disadvantages associated with this method are that the reaction takes place on the paper surface and inevitably produces hydrogen halides, such as HCl, which have negative effects on the paper surface, such as reduced paper strength and coloration. Hydrogen halides are extremely corrosive and are also harmful to manufacturing equipment. For safety reasons, such a configuration is difficult to implement in a paper mill environment.
[0011] Publication WO 2009 / 147283 (Example 1) discloses the functionalization of PVA with 10-undecenoyl chloride in an organic solvent (N-methylpyrrolidone) with a reaction time of 48 hours at room temperature, followed by precipitation of the polymer, purification and final drying.
[0012] Publication WO 2011 / 104427 discloses the functionalization of PVA in a water-based reaction with undecenal. The acetal reaction requires dissolving the PVA in water under acidic conditions to start the reaction and stopping the reaction by a neutralization step.
[0013] Reactions in aqueous solutions are further limited by the reactant concentrations. When the amount of grafting agent is above 2.5 wt%, the solution viscosity begins to rise rapidly, which first complicates and ultimately prevents adequate mixing of the reagents and subsequent handling of the reaction solution. This is particularly problematic for in-line coating processes in paper mills, where the coating machines use pumps that require relatively low viscosity to maintain adequate flow characteristics. Relatively low reaction efficiency is a disadvantage.
[0014] Therefore, existing methods disclose various methods in which the reaction occurs on the surface of a cellulose support or the PVA is dissolved in an organic solvent or water, thereby functionalizing the PVA in solution. Once functionalized, the PVA is in liquid form in solution. The solution is neutralized with an alkaline agent or further purified with other solvents. The disclosed methods also rely on on-site production of the functionalized product or require the processing of multiple types of liquids and / or solvents. PVA is dissolved and functionalized with vinyl-containing molecules, followed by neutralization, separation and / or purification, and combined with possible drying processes, which increases the complexity and economic cost of existing methods. In addition, existing methods have a threshold that limits the amount of vinyl that can be present in the functionalized PVA. Summary of the invention
[0015] The present invention relates to a method for producing a reaction product without adding a solvent, the reaction product comprising a carboxylic acid residue and a thermoplastic polyvinyl alcohol derivative, the thermoplastic polyvinyl alcohol derivative comprising a side chain terminated by a vinyl group. More precisely, the present invention relates to a method in which an organic anhydride and a thermoplastic polyvinyl alcohol containing a hydroxyl group are arranged to undergo a condensation reaction in a molten state. The reaction between the hydroxyl group of the thermoplastic polyvinyl alcohol and the organic anhydride in a molten state is an ester bond forming condensation reaction, which produces a carboxylic acid residue and a thermoplastic polyvinyl alcohol derivative, the thermoplastic polyvinyl alcohol derivative comprising an ester bonded side chain, at least some of which terminate in a vinyl group. By definition, the organic anhydride does not contain water. Aliphatic organic anhydrides are reagents that can undergo an ester bond forming condensation reaction with the hydroxyl group of the thermoplastic polyvinyl alcohol in a very efficient manner. Therefore, a reaction product containing a thermoplastic polyvinyl alcohol derivative and a carboxylic acid residue (i.e., a carboxylic acid) can be obtained, the thermoplastic polyvinyl alcohol derivative having an ester bonded side chain terminated by a vinyl group, the carboxylic acid residue comprising a chain structure terminated by a vinyl group of the same type as the ester bonded side chain. The method is fast and cost-effective. Since the reaction does not require any organic solvent or water, the resulting reaction product also does not require any solvent separation or drying. The reaction product can be simply cooled to a solid reaction product that is easy to transport and store. The reaction is easy to carry out in a reactor (such as an extruder) and therefore does not present mixing problems that may occur in solvent-based reactions.
[0016] The present invention also relates to a solid reaction product containing such a carboxylic acid residue and a thermoplastic polyvinyl alcohol derivative. Some variants relate to a method for making a paper substrate suitable for use as a release liner substrate layer, wherein the paper substrate comprises a primer layer having the reaction product. Some variants relate to a paper substrate comprising a primer layer, wherein the primer layer comprises the reaction product. Some variants relate to the use of the reaction product on a paper substrate suitable for use as a release liner substrate layer.
[0017] The present invention solves the above problems by providing a reaction product comprising a thermoplastic polyvinyl alcohol derivative, wherein the thermoplastic polyvinyl alcohol derivative comprises ester-bonded side chains, at least some of which terminate in vinyl groups. When the thermoplastic polyvinyl alcohol derivative is produced by a molten state reaction, the condensation reaction can be carried out in the absence of a solvent. Therefore, the functionalization of polyvinyl alcohol with an organic anhydride can be arranged to produce a thermoplastic polyvinyl alcohol derivative having side chains, at least some of which terminate in vinyl groups, without being in a solvent.
[0018] When thermoplastic polyvinyl alcohol derivatives are produced by molten state reaction, the reaction can also be further carried out at high temperature, for example, 170°C to 210°C. The reaction in the molten state (which is higher than the melting point of the mixture containing molten polyvinyl alcohol) can occur at a temperature significantly higher than the reaction in an organic solvent or water. The molten state reaction is a favorable method for the ester bond formation condensation reaction of thermoplastic polyvinyl alcohol because thermoplastic polyvinyl alcohol is most stable in the molten state. The term "thermoplastic polyvinyl alcohol" in this context refers to polyvinyl alcohol with thermoplasticity. The risk of polyvinyl alcohol decomposition can be further reduced by selecting a thermoplastic polyvinyl alcohol grade (wherein the degree of hydrolysis is high enough, for example, equal to or higher than 65 moles). However, a grade with a degree of hydrolysis equal to or higher than 90 mole% may not be preferred because excessive heating may also cause polyvinyl alcohol coloring, especially when the hydroxyl content in polyvinyl alcohol is very high. Preferably, when the molten state reaction is carried out with an organic anhydride, the degree of hydrolysis of the thermoplastic polyvinyl alcohol is 65 mole% to 90 mole%. The degree of hydrolysis of 65 mol% to 90 mol% also contributes to the improvement of the thermoplasticity of the polyvinyl alcohol. When the degree of hydrolysis of the thermoplastic polyvinyl alcohol is 65 mol% to 90 mol%, the thermoplastic polyvinyl alcohol is also water-soluble.
[0019] Another advantage of the molten state reaction of polyvinyl alcohol and organic anhydride is that the reaction is independent of pH adjustment. Therefore, no acidic or alkaline reagents are required to adjust the pH before and after the reaction. The use of aliphatic organic anhydrides and thermoplastic polyvinyl alcohol in the molten state reaction can form carboxylic acids as reaction products in addition to thermoplastic polyvinyl alcohol derivatives. Carboxylic acids are weak acids. Therefore, the formation of strong hydrogen halides (such as HCl) can be eliminated. At high temperatures (e.g., 170°C to 210°C), the presence of hydrogen halides in molten polyvinyl alcohol may promote polyene formation, which may promote polyene formation and is a degradation reaction of PVA. As the reaction product is colored, the onset of polyene formation can be visually observed. In addition, hydrogen halides are highly corrosive substances that can easily destroy equipment used to produce thermoplastic polyvinyl alcohol derivatives.
[0020] The molten state reaction can also be used to avoid the purification of the reaction product by adding solvent. Specifically, when preparing a thermoplastic polyvinyl alcohol derivative from a thermoplastic polyvinyl alcohol having a hydroxyl group and wherein the thermoplastic polyvinyl alcohol has been dried, it is not necessary to dissolve the thermoplastic polyvinyl alcohol before the condensation reaction, which reduces the time required for the manufacturing process. Once dried, the thermoplastic polyvinyl alcohol can be simply heated and mixed with a reagent (which is an organic acid anhydride having a chain carbon structure with a vinyl terminal) to obtain a mixture, the temperature of which is higher than the melting point of the mixture, resulting in a reaction in the molten state, wherein at least some of the organic acid anhydride reacts with the hydroxyl group of the thermoplastic polyvinyl alcohol to form a reaction product.
[0021] Since the molten state reaction does not require additional solvent, the reaction volume can be kept small, which simplifies the manufacturing process. The molten state reaction of the mixture can be carried out in a reactor (such as an extruder or a hot and cold mixer), and the mixture contains a molten thermoplastic polyvinyl alcohol with a hydroxyl group and an organic anhydride containing a chain with a vinyl terminal. This is advantageous because the reactor (especially the extruder) is designed to generate high shear forces, which promotes the effective mixing of the participating compounds, thereby affecting the melt viscosity. When measured using standard ISO 1133 (210°C, 2.16kg), the melt flow index of the thermoplastic polyvinyl alcohol derivative is 0.5-300 grams / 10 minutes. Under higher shear forces, the intrachain hydrogen bond formation and interchain hydrogen bond formation risks of polyvinyl alcohol and its derivatives are reduced. Therefore, the method can react in the molten state when carried out in the reactor, wherein, when the gross weight of the mixture is measured, the amount of the reagent is 1% by weight to 10% by weight, more preferably 3% by weight to 6% by weight. Therefore, a thermoplastic polyvinyl alcohol derivative can be obtained, which contains a vinyl molar concentration b vin , when determined by iodine titration according to standard ISO3961:2009(E), b vin The method for producing the polyvinyl alcohol derivative further achieves a shorter reaction duration in the molten state, which may be less than 5 minutes or less, preferably 1 minute or less, and most preferably 20 seconds. The reaction duration may vary depending on the reactor type and the parameters used.
[0022] The method for making a polyvinyl alcohol derivative produces a reaction product that can be extruded and cooled to reduce the temperature of the reaction product and obtain a solid reaction product. The method does not require separation of the reaction product from a solvent. The solid reaction product can be formed into a compact form suitable for transportation, such as granules. The reaction product is easy to store and transport to various places. This enables centralized production of the reaction product, such as in a factory dedicated to the production of polymer products.
[0023] The solid reaction product is stable and can be used for various purposes, for example in a coating composition intended to be applied to a cellulose fiber-based support to form a paper substrate with a primer layer. Preferably, the thermoplastic polyvinyl alcohol with a degree of hydrolysis of 65 to 90 mol% and the formed thermoplastic polyvinyl alcohol derivative with a degree of hydrolysis of 60 to 90 mol%, preferably 65 to 90 mol%, are both water-soluble. The term "water-soluble" in this context means a solution in which the dissolved thermoplastic polyvinyl alcohol or thermoplastic polyvinyl alcohol derivative is obtained within 24 hours after mixing the thermoplastic polyvinyl alcohol or the solid reaction product, respectively, with deionized water in a ratio of at least 1:10 (weight / weight) while continuously stirring at a temperature of 40°C to 80°C. Depending on the temperature used and the shape and size of the material, the time to obtain a solution may vary. Smaller particle sizes and higher temperatures can be used to shorten the time to obtain a solution. When the formed thermoplastic polyvinyl alcohol derivative is water-soluble, the reaction product can be transported to the paper mill in a compact solid form. Thus, the reaction product and / or the thermoplastic polyvinyl alcohol derivative therein can be dissolved and / or diluted with water as desired and / or mixed with other coating composition components as desired. This enables the coating composition to be formed during the manufacture of the paper substrate.
[0024] Therefore, the present invention provides a novel method for shortening the reaction time of grafting PVA. The present invention further realizes that the reaction is carried out without adding solvent, thereby minimizing harmful by-products during the reaction. The present invention also provides a simplified method for producing thermoplastic polyvinyl alcohol derivatives, which contain side chains with vinyl ends. Due to the molten state reaction conditions, the reaction efficiency can be greatly improved. The method can achieve a small reaction volume, which still leads to a high yield of thermoplastic polyvinyl alcohol derivatives, which contain ester-bonded side chains with vinyl ends.
[0025] Provided is a method for producing a thermoplastic polyvinyl alcohol derivative, wherein the thermoplastic polyvinyl alcohol derivative comprises a side chain with a vinyl group at the end, the method comprising the following steps:
[0026] - heating a thermoplastic polyvinyl alcohol having hydroxyl groups, wherein the thermoplastic polyvinyl alcohol has been dried and has a degree of hydrolysis of 65 mol % to 90 mol %, and
[0027] - mixing a reagent with thermoplastic polyvinyl alcohol, wherein the reagent is an organic acid anhydride having a chain carbon structure of at least 4 carbon atoms and a vinyl group at the end,
[0028] Thus, a mixture comprising molten thermoplastic polyvinyl alcohol having hydroxyl groups and an organic acid anhydride containing a vinyl-terminated chain is obtained, and
[0029] - mixing the mixture at a temperature above the melting point of the mixture, thereby causing a reaction in the molten state, wherein at least some of the organic anhydride reacts with the hydroxyl groups of the thermoplastic polyvinyl alcohol in an ester bond forming condensation reaction,
[0030] This results in the formation of a reaction product comprising:
[0031] - carboxylic acid residues from an ester bond-forming condensation reaction, wherein at least some of said carboxylic acid residues contain vinyl-terminated chains, and
[0032] - A thermoplastic polyvinyl alcohol derivative containing ester-bonded side chains, at least some of which are terminated with vinyl groups.
[0033] If desired, the method may further include adding an inhibitor suitable for inhibiting spontaneous free radical polymerization of vinyl, such as butylated hydroxytoluene. In addition, the method may further include adding a catalyst suitable for catalyzing the ester bond forming condensation reaction, such as 1-methylimidazole. The inhibitor and / or catalyst may be added before or during the mixing of the mixture.
[0034] If desired, the method may further comprise removing at least a portion of the carboxylic acid residue from the reaction product during and / or after the condensation reaction (e.g., by evaporation) to obtain a recyclable carboxylic acid residue. At least some of the recyclable carboxylic acid residue may be disposed of in a reaction in which an organic anhydride is formed, thereby arranging for at least partial recovery of the reagent.
[0035] The method may also include: extruding the reaction product and cooling it so that the temperature of the reaction product is reduced and a solid reaction product is obtained; and forming the solid reaction product into a compact form suitable for transportation, such as forming into particles. It is worth noting that the ester bond forming condensation reaction of the organic anhydride always leads to the formation of a carboxylic acid residue, which is thus present in the reaction product. This can be done by first separating the carboxylic acid residue and the thermoplastic polyvinyl alcohol derivative into two separate phases (e.g., by heptane extraction), and then determining the reaction product (e.g., by gas chromatography) after the heptane is evaporated. The carboxylic acid residue produced is generally a carboxylic acid with weaker acidity. Compared with the hydrogen halide produced by the organic halide in the solvent-based reaction, the presence of a carboxylic acid residue is a significant improvement. If necessary, an alkaline agent (e.g., NaOH) can be used to neutralize at least some of the carboxylic acid residues in the reaction product, thereby forming a salt of the carboxylic acid residue, i.e., a carboxylate.
[0036] According to another aspect, the present invention provides a solid reaction product comprising a thermoplastic polyvinyl alcohol derivative comprising an ester-bonded side chain, at least some of which are terminated with a vinyl group, wherein the side chain terminated with a vinyl group comprises a chain carbon structure of at least 4 carbon atoms, and the solid reaction product further comprises a carboxylic acid residue, wherein the carboxylic acid residue is an organic compound comprising a chain carbon structure terminated with a vinyl group of the same type as the side chain of the thermoplastic polyvinyl alcohol derivative. The composition of the carboxylic acid residue may vary depending on the symmetry of the organic anhydride used as a reagent. The melting point of the reaction product may be from 170°C to 210°C. The amount and chemical composition of the carboxylic acid residue in the solid reaction product may vary depending on the mixed organic anhydride, which reacts with the thermoplastic polyvinyl alcohol in an ester bond forming condensation reaction. In addition, some carboxylic acid residues may react with molten thermoplastic polyvinyl alcohol. After the carboxylic acid residue and the thermoplastic polyvinyl alcohol derivative have first been separated into two separate phases, the carboxylic acid residue can be extracted into the heptane phase, for example, by dissolving a small amount of the solid reaction product in distilled water and performing a heptane extraction, since heptane can dissolve fatty acids and is immiscible with water, and the presence of the carboxylic acid residue can be determined from the solid reaction product. The acid residue can also be easily recovered from the heptane by evaporation. After the heptane has been evaporated, the presence of the carboxylic acid residue can be determined, for example, by gas chromatography.
[0037] The solid reaction product can be used as a coating composition. When the reaction product is in the form of a solid concentrate, the reaction product is stable, compact and easy to transport and store globally under any conditions. It can be dissolved and / or diluted to a desired concentration for a variety of applications. The solid reaction product can be used as a coating composition. When needed, the reaction product in solid form or when dissolved can also be mixed with other coating composition materials. For example, the amount of the thermoplastic polyvinyl alcohol derivative of the reaction product can be 80% by weight to 99.9% by weight of the reaction product.
[0038] The reagent in the method can be an aliphatic organic anhydride, and is a symmetrical anhydride or an asymmetrical anhydride with at least one acyl group, which has a chain carbon structure of at least 4 carbon atoms and a vinyl group at the end. Preferably, the chain carbon structure contains 5 or more, preferably at least 9, and most preferably 10 to 18 carbon atoms. Preferably, the organic anhydride is an anhydride based on fatty acids, which may contain one or two acyl groups derived from the following substances: 3-butenoic acid, 2,2'-dimethyl-4-pentenoic acid, 4-pentenoic acid, 7-octenoic acid, 8-nonenoic acid, 10-undecenoic acid or 12-tridecenoic acid. For example, the reagent can be undecenoyl anhydride, which is a symmetrical anhydride containing two identical acyl groups that can be derived from 10-undecenoic acid, and each acyl group has a vinyl group at the end. The aliphatic anhydride used as a reagent in the method can be manufactured by, for example, reacting a carboxylate having a chain carbon structure of at least 4 carbon atoms and a vinyl group at the end with an acyl chloride. The carboxylate can be, for example, sodium carboxylate. Alternatively, the reagent can be obtained by reacting acetic anhydride with a carboxylic acid having a chain carbon structure of at least 4 carbon atoms and terminating in a vinyl group. If desired, acetic anhydride can be reacted with a mixture of carboxylic acids to obtain a heterogeneous reagent comprising more than one type of aliphatic anhydride, at least some of which have a chain carbon structure of at least 4 carbon atoms and terminating in a vinyl group.
[0039] According to another aspect, there is provided a paper substrate suitable for bonding silicone in a catalytic hydrosilation reaction, the paper substrate comprising:
[0040] - a cellulose fiber-based support layer; and
[0041] - a primer layer containing a thermoplastic polyvinyl alcohol derivative containing ester-bonded side chains, at least some of which have vinyl groups as terminals,
[0042] The ester-bonded side chain with a vinyl end contains a chain carbon structure of at least 4 carbon atoms, the primer layer also contains a carboxylic acid residue and / or a salt of the carboxylic acid residue, and the carboxylic acid residue and / or the salt of the carboxylic acid residue is an organic compound containing a chain carbon structure of at least 4 carbon atoms with a vinyl end of the same type as the ester-bonded side chain.
[0043] According to another aspect, there is provided a method of making a paper substrate suitable for bonding silicone in a catalytic hydrosilation reaction, the method comprising the steps of:
[0044] - heating a thermoplastic polyvinyl alcohol having hydroxyl groups, wherein the thermoplastic polyvinyl alcohol has been dried and has a degree of hydrolysis of 65 mol % to 90 mol %, and
[0045] - mixing a reagent with thermoplastic polyvinyl alcohol, wherein the reagent is an organic acid anhydride, the organic acid anhydride having at least one chain having a chain carbon structure of at least 4 carbon atoms and a vinyl group at the end,
[0046] thereby obtaining a mixture containing molten thermoplastic polyvinyl alcohol having hydroxyl groups and an organic anhydride containing a chain terminated by a vinyl group, and - subjecting the mixture to mixing at a temperature above the melting point of the mixture, thereby causing a reaction in a molten state, wherein at least some of the organic anhydride reacts with the hydroxyl groups of the thermoplastic polyvinyl alcohol in an ester bond forming condensation reaction,
[0047] This results in the formation of a reaction product comprising:
[0048] o carboxylic acid residues from an ester bond forming condensation reaction, wherein at least some of the carboxylic acid residues contain vinyl terminated chains, and
[0049] o a thermoplastic polyvinyl alcohol derivative containing ester-bonded side chains, at least some of which terminate in vinyl groups; and
[0050] - coating at least one side of a cellulose fiber-based support layer with a coating composition comprising the reaction product,
[0051] Thus, a paper substrate having a primer layer is formed, wherein the primer layer comprises a thermoplastic polyvinyl alcohol derivative, wherein the thermoplastic polyvinyl alcohol derivative comprises at least some ester-bonded side chains terminated with vinyl groups, wherein the side chains terminated with vinyl groups comprise a chain-like carbon structure of at least 4 carbon atoms, and the primer layer further comprises a carboxylic acid residue, wherein the carboxylic acid residue is an organic compound, wherein the organic compound comprises a chain-like carbon structure of at least 4 carbon atoms terminated with vinyl groups of the same kind as the side chains of the thermoplastic polyvinyl alcohol derivative,
[0052] Therefore, paper substrates are suitable for bonding silicones in catalytic hydrosilation reactions.
[0053] Preferably, the paper substrate is a calendered industrial paper. The calendering process may include the use of a calender, a multi-grip calender and / or a super calender to modify the surface properties of the paper and / or to bring the paper to a final thickness. Such a calendered paper substrate can be used as a release liner. Preferably, the cellulose fiber-based support layer is a glass paper, a super calendered kraft (SCK) paper or a clay coated kraft (CCK) paper. Preferably, the smoothness of the paper substrate is at least 900 seconds / minute (according to ISO 5627), and / or the density is at least 1.0, for example 1.0 to 1.2, wherein the density refers to the number of grams per unit thickness (according to ISO 534) (ISO 536), and / or the porosity is equal to or less than 15000 pm / Pas (according to ISO 11004), and / or when the paper weight is less than 70g / m 2 When the transparency is equal to or higher than 40%, preferably equal to or higher than 44%, or when the paper weight is equal to or higher than 70g / m 2 When the transparency is equal to or higher than 28%, preferably equal to or higher than 33% (according to ISO 2470).
[0054] The reaction product can be stored as a solid reaction product before use in a coating composition. The reaction product in solid form or dissolved can also be mixed with other coating composition materials. Thus, the reaction product or an aqueous reaction product solution formed from the solid reaction product can be used to coat at least one side of the cellulose fiber-based support layer.
[0055] It has been observed that vinyl-containing carboxylic acid residues obtainable by ester bond-forming condensation reactions between organic anhydrides and thermoplastic polyvinyl alcohols having hydroxy groups act as surfactants on paper substrates. This effect is observed even if some of the carboxylic acid residues on the primer layer have been neutralized to the corresponding carboxylates, i.e., salts of the carboxylic acid residues. When disposed on the primer layer of a paper substrate, the carboxylic acid residues can be configured to improve the subsequent spreading of a silicone-based composition that can be applied as a release coating on the paper substrate. Thus, the reaction product of the ester bond-forming condensation reaction in the molten state can be used to obtain a paper substrate having improved surface properties.
[0056] Other advantages of the above disclosed method and its products are explained in more detail in the following description with reference to the attached drawings.
[0057] BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1a and 1b By way of example, a method for producing a thermoplastic polyvinyl alcohol derivative in a melt state reaction is shown;
[0059] Figure 2a and 2bOptional features of a method for making a thermoplastic polyvinyl alcohol derivative in a melt state reaction are shown by way of example;
[0060] Figure 3a and 3b A method of making a paper substrate suitable for bonding silicone in a catalytic hydrosilation reaction is shown by way of example;
[0061] Figure 4 By way of example, a cross-sectional view of a release liner comprising a paper substrate and a release layer is shown;
[0062] Figure 5 By way of example, a cross-sectional view of a label laminate web manufactured on a release liner is shown;
[0063] Figure 6 By way of example, the general formula and some variants of an organic acid anhydride having at least one acyl group, having a chain carbon structure of at least 4 carbon atoms and a vinyl group at the end, which is suitable for use as a reagent in a method for producing a thermoplastic polyvinyl alcohol derivative by a molten state reaction;
[0064] Figure 7 An ester bond forming condensation reaction between an organic anhydride and a thermoplastic polyvinyl alcohol in a molten state is shown by way of example, wherein at least some of the organic anhydride reacts with the hydroxyl groups of the thermoplastic polyvinyl alcohol in the ester bond forming condensation reaction, thereby forming a reaction product containing a carboxylic acid residue and a thermoplastic polyvinyl alcohol derivative, wherein at least some of the carboxylic acid residue contains a chain terminated with a vinyl group, and at least some of the ester bonded side chains terminate with a vinyl group;
[0065] Figure 8 By way of example, an ester bond forming condensation reaction between undecylenic anhydride (which is a symmetrical anhydride containing two identical acyl groups derivable from 10-undecylenic acid, each acyl group having a vinyl group at the end) and thermoplastic polyvinyl alcohol in a molten state is shown, wherein at least some of the undecylenic anhydride reacts with the hydroxyl group of the thermoplastic polyvinyl alcohol in the ester bond forming condensation reaction, thereby forming a reaction product containing a 10-undecylenic acid residue and a thermoplastic polyvinyl alcohol derivative, wherein at least some of the ester bonded side chains have a vinyl group at the end;
[0066] Fig. 9 The ester bond forming condensation reaction between acetyl undecylenic anhydride (which is an asymmetric anhydride containing one acyl group derivable from 10-undecylenic acid having a vinyl group at the terminal and another acyl group derivable from acetic acid) and thermoplastic polyvinyl alcohol in a molten state is shown by way of example, wherein at least some of the acetyl undecylenic anhydride reacts with the hydroxyl group of the thermoplastic polyvinyl alcohol in the ester bond forming condensation reaction, thereby forming a reaction product containing acetic acid residues, 10-undecylenic acid residues and a thermoplastic polyvinyl alcohol derivative, wherein at least some of the ester bonded side chains have vinyl groups at the terminals.
[0067] Symbol S in the accompanying drawings x and S z The drawings are illustrative and are intended to provide a better understanding of the basic invention. The drawings are not drawn to any particular scale. DETAILED DESCRIPTION OF THE INVENTION
[0069] Thermoplastic polyvinyl alcohol and organic anhydride
[0070] In this article, thermoplastic polyvinyl alcohol refers to polyvinyl alcohol having hydroxyl groups and a degree of hydrolysis of 65 mol % to 90 mol %. The degree of hydrolysis is also called saponification, and in this article it means the molar percentage of acetyl groups of polyvinyl acetate that has been hydrolyzed to hydroxyl groups when producing polyvinyl alcohol. Therefore, a degree of hydrolysis of 100 mol % means that the polyvinyl alcohol does not contain acetyl groups. As used herein, thermoplastic polyvinyl alcohol refers to polyvinyl alcohol with thermoplasticity. Thermoplastic polyvinyl alcohol is processed in a molten state. The molten state processability of thermoplastic polyvinyl alcohol can be used to reduce the surface porosity of paper substrates. A degree of hydrolysis of 65 mol % to 90 mol % contributes to the improvement of the thermoplasticity of polyvinyl alcohol. Completely hydrolyzed polyvinyl alcohol (e.g., polyvinyl alcohol with a degree of hydrolysis exceeding 95 mol %) is less desirable because the melting point temperature of fully hydrolyzed polyvinyl alcohol is close to the decomposition point temperature, which makes the processing of polyvinyl alcohol in a molten state less feasible. In addition, in fully hydrolyzed polyvinyl alcohol, heat treatment often causes increased crystallization, which in turn weakens its solubility in water. When providing a coating composition for a cellulosic fiber-based support layer, reduced water solubility may be detrimental to the end use of the product, where the product advantageously dissolves in water.
[0071] In this article, dried thermoplastic polyvinyl alcohol refers to dried thermoplastic polyvinyl alcohol PVA1, that is, the material that has been dried before use so that the water content of the material when it is intended to be used is less than 2% by weight, preferably less than 1% by weight, for example less than 0.5% by weight, preferably less than 0.1% by weight or most preferably less than 0.01% by weight. Once the package is opened, commercially available thermoplastic polyvinyl alcohol grades can absorb moisture from the air. In order to obtain dry thermoplastic polyvinyl alcohol, conventional methods can be used to remove moisture, such as a circulating air dryer. At a temperature of 60°C-80°C, the typical drying time of thermoplastic polyvinyl alcohol PVA1 is 6-8 hours. The moisture content of thermoplastic polyvinyl alcohol PVA1 can be measured immediately before use, for example by using an infrared moisture analyzer.
[0072] Organic anhydrides refer to organic compounds having two acyl groups bonded to the same oxygen atom. The organic anhydride participating in the ester bond forming condensation reaction should have an acyl group having a chain carbon structure with a carbon chain length of at least 4 carbon atoms, and a vinyl group at the end. The acyl group can therefore form an ester bond with the hydroxyl group of the thermoplastic polyvinyl alcohol in the condensation reaction. Chain carbon structures with a chain length of less than 4 carbon atoms in the organic anhydride hydrocarbon chain are not suitable because the short chain length may interfere with the thermoplastic polyvinyl alcohol during the ester bond forming condensation reaction. Preferably, the chain carbon structure contains 5 or more, preferably at least 9, and most preferably 10 to 18 carbon atoms. Longer chain lengths are not ideal because they may cause chain folding problems during or after the ester bond forming condensation reaction. The organic anhydride can be aliphatic and be a symmetrical anhydride or an asymmetrical anhydride. The symmetrical anhydride used herein refers to an anhydride having two identical acyl groups, each acyl group ending in a vinyl group. The asymmetrical anhydride used herein refers to an anhydride having non-identical acyl groups, wherein at least one acyl group ends in a vinyl group. Such as Figure 6 As shown, in the asymmetric anhydrides AH1, AH3, and AH5, the two acyl groups of the anhydrides are different. In the symmetric anhydrides AH2 and AH4, the two acyl groups of the anhydrides are the same. Symbol R 1 and R 2 Each of them represents a functional group individually, at least one or both of which have a chain carbon structure with a carbon chain length of at least 3 carbon atoms, and a vinyl group at the end. Figure 7 , 8 As shown in Figures 9 and 10, when the aliphatic organic anhydride AH1; AH2; AH3; AH4; AH5 undergoes a condensation reaction with the hydroxyl group of the thermoplastic polyvinyl alcohol PVA1 in a molten state, one of the acyl groups forms an ester bond with the hydroxyl group of the polyvinyl alcohol PVA1, and the other acyl group becomes a carboxylic acid residue RD1; RD2; RD3. The formed thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3 therefore contains at least some ester-bonded side chains with vinyl ends, wherein the side chains with vinyl ends contain a chain carbon structure of at least 4 carbon atoms. Statistically, any acyl group in the aliphatic anhydride is equally likely to participate in the ester bond-forming condensation reaction. Therefore, the carboxylic acid residue RD1; RD2; RD3 is an organic compound containing a chain carbon structure of at least 4 carbon atoms with vinyl ends of the same type as the ester-bonded side chains of the thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3.
[0073] The organic anhydride used as a reagent in the method can be manufactured by, for example, reacting a carboxylate having a chain carbon structure of at least 4 carbon atoms and a vinyl group at the end with an acyl chloride. The carboxylate can be, for example, a sodium carboxylate. Alternatively, the reagent can be obtained by reacting acetic anhydride with a carboxylic acid having a chain carbon structure of at least 4 carbon atoms and a vinyl group at the end. If desired, acetic anhydride can react with a carboxylic acid mixture to obtain a heterogeneous reagent comprising more than one type of aliphatic anhydride, at least some of which have a chain carbon structure of at least 4 carbon atoms and a vinyl group at the end. An exemplary method for manufacturing an aliphatic organic anhydride is a continuous countercurrent process carried out in a fractionating tower, wherein an aliphatic acid entering the tower near the top of the tower flows downward along the tower, thereby being configured to countercurrently rise with the acetic anhydride vapor introduced from the bottom of the tower. When the two compounds meet each other, the fatty acid is converted into the corresponding anhydride, and the acetic anhydride vapor rising through the tower is converted into acetic acid. The aliphatic anhydride formed in the reaction can be collected from the bottom of the tower by distillation. By selecting an aliphatic acid having a chain carbon structure of at least 4 carbon atoms and a vinyl group at the end, the same chain carbon structure of at least 4 carbon atoms at the end of the vinyl group can be introduced into the formed acid anhydride.
[0074] Chain carbon structure is used to represent a series of bonded carbon atoms, wherein the carbon atoms are bonded to other carbon atoms. Known carbon is suitable for catenation, and catenation refers to forming a chain with interconnected carbon-carbon bonds in this article. Chain carbon structure may also be referred to as catenae. In this article, chain carbon structure includes hydrocarbon chain. Chain carbon structure may also include substituents, such as oxygen, hydrogen or alkane or alkenyl, such as vinyl. Chain carbon structure may have 4 or more interconnected carbon atoms in series. Chain carbon structure may be branched. Preferably, chain carbon structure is a hydrocarbon chain with at least 7 carbon atoms, more preferably 11 carbon atoms and end with a functional vinyl group.
[0075] A method for producing thermoplastic PVA derivatives in a molten state
[0076] See also Figure 1a , 1b , which exemplifies a method for producing a thermoplastic polyvinyl alcohol derivative comprising an ester-bonded side chain with a vinyl terminal. See also Figure 6 , which shows organic anhydrides suitable for use as reagents in the method. Figures 7 to 9, which illustrates an ester bond forming condensation reaction between an organic anhydride and a thermoplastic polyvinyl alcohol in a molten state, wherein heat Δ provided to the system causes the reaction to occur. The molten state condensation reaction of the organic anhydride AH1; AH2; AH3; AH4; AH5 and the thermoplastic polyvinyl alcohol PVA1 containing hydroxyl groups can be provided by heating HT1 the solid thermoplastic polyvinyl alcohol PVA1 having hydroxyl groups, wherein the thermoplastic polyvinyl alcohol PVA1 has been dried and has a degree of hydrolysis of 65 mol% to 90 mol%. By mixing the reagent RGT1 (which is an organic anhydride AH1; AH2; AH3; AH4; AH5) with the thermoplastic polyvinyl alcohol PVA1 at a temperature above the melting point of the mixture MXT1 AD1, thereby obtaining the mixture MXT1, a reaction in a molten state can be arranged, wherein at least part of the hydroxyl groups of the organic anhydride AH1; AH2; AH3; AH4; AH5 and the thermoplastic polyvinyl alcohol PVA1 undergo an ester bond forming condensation reaction. Mixing MR1 with the mixture MXT1 at a temperature above the melting point of the mixture MXT1 contributes to the reaction rate and better mixing. Typically, a temperature in the range of 170°C to 210°C can be used for the condensation reaction. The lower limit of the suitable temperature range is limited by the melting points of the thermoplastic polyvinyl alcohol PVA1 and the mixture MXT1. The upper limit of the suitable temperature range is limited by the decomposition temperature of the polyvinyl alcohol PVA1 and / or its derivatives CMP1; CMP2; CMP3. Preferably, the temperature during the condensation reaction in the molten state is 170°C to 210°C. Most preferably, the temperature is 170°C to 190°C, which reduces the possibility of thermal decomposition of the thermoplastic polyvinyl alcohol PVA1 and / or its derivatives CMP1; CMP2; CMP3. It is preferred to carry out the reaction in the molten state without adding a solvent. The absence of an added solvent results in a small reaction volume. The lack of solvent and acid halide in the reaction in the molten state further avoids the formation of corrosive residues such as HCl in the reaction product.
[0077] When the reagent RGT1 is an organic anhydride AH1; AH2; AH3; AH4; AH5 having at least one chain (the chain has a chain carbon structure of at least 4 carbon atoms and is terminated with a vinyl group), a reaction product PROD1 can be formed, wherein the reaction product PROD1 contains carboxylic acid residues RD1; RD2; RD3 of an ester bond forming condensation reaction and thermoplastic polyvinyl alcohol derivatives CMP1; CMP2; CMP3, wherein at least some of the carboxylic acid residues contain chains terminated with a vinyl group, and the thermoplastic polyvinyl alcohol derivatives CMP1; CMP2; CMP3 contain at least some ester-bonded side chains terminated with a vinyl group. Figure 1a As shown, the dried thermoplastic polyvinyl alcohol PVA1 can first be mixed with the reagent RGT1 AD1. Figure 1bAs shown, it is also possible to first arrange to heat the dried thermoplastic polyvinyl alcohol PVA1 HT1 and then arrange to mix AD1 with the reagent RGT1. It is preferred to first heat HT1 and then mix AD1 because this is conducive to forming a uniformly melted thermoplastic polyvinyl alcohol PVA1. It is ideal that the quality of the molten thermoplastic polyvinyl alcohol PVA1 is uniform to ensure good conditions for the ester bond formation condensation reaction.
[0078] Heating HT1 of thermoplastic polyvinyl alcohol PVA1 before mixing AD1 further promotes the improvement of reaction rate and plasticity, which helps to better mix MR1, thereby improving production efficiency. For example, a simple industrial extruder can produce up to 1000kg of reaction product PROD1 in one hour. The duration of the reaction in the molten state can be less than 5 minutes, preferably less than 1 minute, and more preferably less than 20 seconds. The duration includes the heating HT1 of thermoplastic polyvinyl alcohol PVA1 and the formation of reaction product PROD1. Mixing MR1 is carried out in a reactor. This is also the step of reacting in the molten state. Mixing can be carried out in an extruder or a hot and cold mixer, which is convenient to provide enough energy for heating HT1 and / or provide enough shear force for mixing MR1. When the reaction product PROD1 is manufactured in a molten state in an extruder, even if a large amount of reagent RGT1 is used to mix with PVA, the reaction viscosity can be easily controlled. An extruder is a device designed for processing high-viscosity glue loading. Various types of extruders are commercially available and well known in the art. The common name of the melt extruder includes screw extruder, extrusion reactor or extruder. The example of suitable commercially available extruder includes single screw extruder, twin screw extruder and multi-screw extruder. Preferably, the method is carried out in a twin screw extruder, which brings the advantages of more uniform shearing, greater screw conveying capacity and more stable extrusion. More preferably, the method according to the present invention is carried out in a co-rotating twin screw extruder to achieve better mixing. Compared with known methods such as water-based synthesis in which a large amount of water (up to thousands of kilograms) needs to be used and removed (for example by evaporation), using molten state reaction in a suitable reactor (such as an extruder) has considerable advantages. In contrast, molten state reaction can be carried out in a large amount by compact devices in a short time, thereby realizing centralized production, and solid water-soluble reaction products are easily distributed to paper mills all over the world.
[0079] When a twin-screw extruder is used, the dried thermoplastic polyvinyl alcohol PVA1 can be fed into the barrel of the extruder (for example, from a hopper), so that the thermoplastic polyvinyl alcohol PVA1 is gradually melted by a heating HT1 source arranged along the barrel. The reagent RGT1 can be fed from the same source or another source (such as another hopper or a side feeder unit or a liquid feed unit), in which case the thermoplastic polyvinyl alcohol PVA1 can be mixed with the reagent RGT1 AD1 before heating HT1. When the reagent RGT1 is fed from another source downstream of the extruder barrel, the thermoplastic polyvinyl alcohol PVA1 can be at least partially heated HT1 to a molten state before mixing the reagent RGT1 AD1. The latter case is more preferred because more friction can be provided, thereby promoting uniform melting of the material into molten thermoplastic polyvinyl alcohol PVA1.
[0080] See also Figure 2a and 2b , which shows optional features in a method for making thermoplastic polyvinyl alcohol derivatives in a molten state reaction. If necessary, inhibitor IHB1 can be used to inhibit spontaneous free radical polymerization of vinyl and / or inhibit crosslinking reactions of thermoplastic polyvinyl alcohol PVA1 and / or its derivatives CMP1; CPM2; CMP3. An example of the inhibitor IHB1 is butylated hydroxytoluene, which can be used as a free radical scavenger to inhibit free radical reactions (such as polymerization and crosslinking). Inhibitor IHB1 can be added before mixing MR1 or during mixing MR1, that is, before the ester bond forming condensation reaction or during the ester bond forming condensation reaction. When used, inhibitor IHB1 is generally added in a small amount, for example, an amount equal to or less than 0.2 weight % of the total weight of the mixture MXT1.
[0081] Furthermore, if desired, a homogeneous or heterogeneous catalyst CAT1 can be used to accelerate the ester bond forming condensation reaction. Suitable catalysts CAT1 can be, for example, Bronsted acids (e.g., sulfuric acid), Lewis acids (e.g., tin(II) octoate) or Bronsted / Lewis bases (e.g., alkali metal alkoxides or carbonates). In addition, pyridine can be used as the catalyst. A preferred catalyst CAT1 is 1-methylimidazole, which has a high catalytic activity, which is 4x10 higher than that of pyridine. 2 The catalyst CAT1 can be added before or during the mixing of MR1, that is, before or during the ester bond forming condensation reaction. When used, the catalyst CAT1 is usually added in a small amount, for example, an amount equal to or less than 0.5% by weight of the total weight of the mixture MXT1.
[0082] The ester bond forming condensation reaction of organic anhydride AH1; AH2; AH3; AH4; AH5 and thermoplastic polyvinyl alcohol PVA1 containing hydroxyl group in the molten state produces a reaction product PROD1, wherein the reaction product PROD1 contains thermoplastic polyvinyl alcohol derivatives CMP1; CMP2; CMP3 and carboxylic acid residues RD1; RD2; RD3 of the ester bond forming condensation reaction, such as Figures 7 to 9 shown.
[0083] See also Figure 7 When heat △ is applied to a mixture containing thermoplastic polyvinyl alcohol PVA1 and organic acid anhydride AH1 so that the temperature of the mixture is higher than the melting point of the mixture, an ester bond forming condensation reaction in a molten state begins to occur. During the condensation reaction, one of the two acyl groups of the organic acid anhydride AH1 forms an ester bond with the hydroxyl group of the thermoplastic polyvinyl alcohol PVA1, thereby forming a thermoplastic polyvinyl alcohol derivative CMP1, while the other acyl group becomes a carboxylic acid residue RD1. The condensation reaction of the organic acid anhydride AH1 in a molten state is non-selective, so that any acyl group can participate in the ester bond forming reaction. Each acyl group comprises a 2 and R 1 The ester bond forming condensation reaction thus produces a thermoplastic polyvinyl alcohol derivative CMP1, which contains a functional group R 1 and R 2 The ester bond formation condensation reaction further forms a functional group R 1 and R 2 The carboxylic acid residue RD1. When the functional group R 1 ; R 2 At least one of the chains has a vinyl terminal, and the same functional group R 1 ; R 2 It is present in the thermoplastic polyvinyl alcohol derivative CMP1 and the carboxylic acid residue RD1.
[0084] Further references Figure 7 The ester bond forming condensation reaction between the molten thermoplastic polyvinyl alcohol PVA1 and the asymmetric organic anhydride AH1 (without the addition of solvent) produces a reaction product PROD1 containing a carboxylic acid residue RD1 and a thermoplastic polyvinyl alcohol derivative CMP1. 1 and R 2At least one of the anhydrides has a vinyl-terminated chain, so at least some of the resulting carboxylic acid residues RD1 contain vinyl-terminated chains, and at least some of the thermoplastic polyvinyl alcohol derivatives CMP1 contain vinyl-terminated ester-bonded side chains. Statistically, the probability of any acyl group in the acid anhydride participating in the ester bond-forming condensation reaction is the same. Therefore, the carboxylic acid residues RD1; RD2; RD3 are organic compounds containing a chain carbon structure of at least 4 carbon atoms terminated in a vinyl group of the same type as the ester-bonded side chains of the thermoplastic polyvinyl alcohol derivatives CMP1; CMP2; CMP3. In addition, see Figure 6 , when the asymmetric organic anhydrides AH1; AH3; AH5 react in an ester bond condensation reaction, any acyl group may also become an ester bond side chain of the thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3. Therefore, the advantage of using symmetrical anhydrides AH2; AH4 is that a thermoplastic polyvinyl alcohol derivative CMP1; CMP2 is obtained, and the thermoplastic polyvinyl alcohol derivative CMP1; CMP2 may contain a larger amount of ester bond side chains with vinyl ends than the thermoplastic polyvinyl alcohol derivative CMP3, wherein the asymmetric anhydrides AH1; AH3; AH5 are used unless both acyl ends in the asymmetric anhydride become vinyl. This is shown in Fig. 9 , wherein an ester bond forming condensation reaction in a molten state between a molten thermoplastic polyvinyl alcohol PVA1 and acetyl undecylenic anhydride AH5 (which is an asymmetric organic anhydride) produces a reaction product PROD1 containing a carboxylic acid residue RD3 and a thermoplastic polyvinyl alcohol derivative CMP3. Although not shown in Fig. 9 However, the condensation reaction of acetyl undecylenic anhydride AH5 with the hydroxyl groups of thermoplastic polyvinyl alcohol is non-selective. Therefore, the carboxylic acid residue RD3 contains acetic acid and 10-undecylenic acid with a vinyl terminal. Similarly, see Figure 8 , the ester bond forming condensation reaction in the molten state between the molten thermoplastic polyvinyl alcohol PVA1 and the undecylenic anhydride AH4 (which is a symmetrical organic anhydride) produces a reaction product PROD1 containing a carboxylic acid residue RD2 and a thermoplastic polyvinyl alcohol derivative CMP2. However, since both acyl groups of the undecylenic anhydride AH4 have a linear chain with a vinyl terminal, the obtained carboxylic acid residue RD2 contains only a linear chain with a vinyl terminal, and the thermoplastic polyvinyl alcohol derivative CMP2 contains an ester-bonded side chain with a vinyl terminal.
[0085] The reagent RGT1 can be mixed with the thermoplastic polyvinyl alcohol PVA1 AD1 in an amount of 1 wt % to 10 wt %, more preferably 3 wt % to 6 wt %, when the total weight of the mixture MXT1 is measured. Larger amounts of the reagent RGT1 may reduce the melt viscosity of the mixture to a certain extent, complicating the operation of the reactor, especially when the reactor is an extruder.
[0086] See also Figure 6 , the reagent RGT1 may include one or more organic anhydrides, which may be different. The organic anhydrides AH1; AH2; AH3; AH4; AH5 may be anhydrides based on fatty acids. As described herein, the anhydrides based on fatty acids include at least one chain having a chain carbon structure of at least 4 carbon atoms with a vinyl group at the end. The organic anhydride may be a symmetrical or asymmetrical anhydride. The anhydride based on fatty acids may include one or two acyl groups derived from the following substances: 3-butenoic acid, 2,2'-dimethyl-4-pentenoic acid, 4-pentenoic acid, 7-octenoic acid, 8-nonenoic acid, 10-undecenoic acid or 12-tridecenoic acid. Symmetric fatty acid-based anhydrides may be derived from a single fatty acid. Asymmetric fatty acid-based anhydrides may be derived from two or more different fatty acids. For example, the organic anhydride may be acetyl undecenoic anhydride AH5, which is an asymmetrical anhydride comprising an acyl group having a vinyl group, wherein the acyl group is derived from 10-undecenoic acid. Alternatively or additionally, the organic anhydride may be undecenoic anhydride AH4, which is a symmetrical anhydride comprising two identical acyl groups each having a vinyl group at the end, wherein the two acyl groups are derived from 10-undecenoic acid; or 4-pentenooctanoic anhydride AH3, wherein one acyl group is derived from 4-pentenoic acid.
[0087] See also Figure 2a and 2b , after forming the reaction product PROD1, it can be extruded EX1, for example, through a die. The extrudate can be cooled, preferably cooled by air or an inert gas stream, so that the temperature of the reaction product is reduced and a solid reaction product OBJ1 is obtained. Air cooling can be used to control the temperature drop rate of the reaction product PROD1. When the temperature drop rate of the reaction product PROD1 is small, the reaction product PROD1 can be configured to keep a longer time at a temperature higher than the melting point of the mixture MXT1. This can extend the time of the condensation reaction, thereby increasing the yield of the reaction product. Alternatively, cooling can be performed, for example, by water bath cooling. The solid reaction product OBJ1 can be formed into a compact form suitable for transportation, such as pellets, granulates or powders.
[0088] The method thus achieves an efficient and concise method for producing a solid reaction product by a molten state reaction, wherein no separation and / or purification of the reaction product is required. The solid reaction product is easily formed into a granular or powder form for transportation. The solid reaction product can be later dissolved in water, for example, when used to prepare a coating composition.
[0089] Acidic residues are recycled into reagents
[0090] See also Figure 2a and Figure 2bOptionally, during and / or after the ester bond forming condensation reaction, at least part of the carboxylic acid residues RD1; RD2; RD3 from the reaction product PROD1 can be removed, for example, by evaporation. Thus, a recyclable carboxylic acid residue RRD1 can be obtained. The carboxylic acid residue can be evaporated while the reaction product is extruded. The vapor containing the evaporated carboxylic acid residue can be collected and condensed into a liquid state for recycling. For recycling purposes, the recyclable carboxylic acid residue RRD1 can be arranged to participate in a reaction in which an organic anhydride AH1; AH2; AH3; AH4; AH5 is formed, which has at least one chain having a chain carbon structure of at least 4 carbon atoms and a vinyl group at the end, thereby forming a reagent RGT1 for the recyclable carboxylic acid residue RRD1. Thus, at least part of the carboxylic acid residues RD1; RD2; RD3 can be recycled. The possibility of recycling chemical substances can be used to further reduce the cost of the manufacturing steps. Recycling is also a sustainable method for providing reagents for the method of manufacturing thermoplastic polyvinyl alcohol derivatives.
[0091] See also Figure 3b Optionally, the method may further comprise: using an alkaline reagent BASE1 (e.g. NaOH) to neutralize at least some of the carboxylic acid residues RD1; RD2; RD3 in the reaction product, thereby forming a salt of the carboxylic acid residue. When the pH of the reagent is higher than the pH of the reaction product PROD1 or the solid form reaction product OBJ1 or the aqueous solution PR1 formed by the solid reaction product OBJ1, other reagents containing sodium may also be used for neutralization. The carboxylic acid residues RD1; RD2; RD3 are generally less acidic carboxylic acids than the hydrogen halide produced according to known methods. Neutralization makes the reaction product less harmful. According to the present invention, the salt content is less compared to the above-mentioned known methods in the prior art.
[0092] Reaction products
[0093] As described above, the molten state reaction of the thermoplastic polyvinyl alcohol PVA1 having a hydroxyl group and the organic acid anhydride AH1; AH2; AH3; AH4; AH5 containing a chain terminated with a vinyl group can be configured to provide a solid reaction product OBJ1 containing a thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3 and a carboxylic acid residue RD1; RD2; RD3. Due to the non-selective ester bond forming condensation reaction in the molten state, the thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3 and the carboxylic acid residue RD1; RD2; RD3 can contain the same type of chain carbon structure of at least 4 carbon atoms terminated with a vinyl group. More specifically, the solid reaction product OBJ1 contains the thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3, and the thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3 contains at least some ester-bonded side chains terminated with a vinyl group, wherein the side chain terminated with a vinyl group contains a chain carbon structure of at least 4 carbon atoms. The solid reaction product OBJ1 also contains carboxylic acid residues RD1; RD2; RD3, wherein the carboxylic acid residues RD1; RD2; RD3 are organic compounds that also contain a chain carbon structure of at least 4 carbon atoms terminated with a vinyl group of the same type as the side chains of the thermoplastic polyvinyl alcohol derivatives CMP1; CMP2; CMP3. The amount of the thermoplastic polyvinyl alcohol derivatives CMP1; CMP2; CMP3 can be 80.0 wt% to 99.9 wt% of the solid reaction product OBJ1. The melting point of the solid reaction product OBJ1 can be 170°C to 210°C. The solid reaction product OBJ1 is treated with a neutralizing agent (e.g., NaOH). Therefore, at least some of the carboxylic acid residues RD1; RD2; RD3 can be in the form of a carboxylate salt. The solid reaction product can be dissolved in water and diluted to the desired / required concentration for a variety of applications. The solid reaction product OBJ1 can be used to form an aqueous solution that can be used as a coating composition. The solid reaction product OBJ1 can be used to form a coating composition, the coating composition containing thermoplastic polyvinyl alcohol derivatives CMP1; CMP2; CMP3, the thermoplastic polyvinyl alcohol derivatives CMP1; CMP2; CMP3 containing at least some ester-bonded side chains with vinyl ends, wherein the side chains with vinyl ends contain a chain carbon structure of at least 4 carbon atoms; the coating composition can also contain carboxylic acid residues RD1; RD2; RD3. When mixed with other coating composition materials, the solid reaction product can be used as part of the coating composition.
[0094] The degree of hydrolysis of the thermoplastic polyvinyl alcohol derivative contained in the reaction product can be 60% to 90%. The thermoplastic polyvinyl alcohol derivative contained in the reaction product can also have a melt flow index of 0.5 g / 10 min to 300 g / 10 min. The melt flow index is measured according to standard ISO 1133 (210° C., 2.16 kg) using a melting point measuring device or by using differential scanning calorimetry.
[0095] The thermoplastic polyvinyl alcohol derivative contained in the reaction product may further comprise a vinyl molar concentration b vin , which is equal to or higher than 0.01 mmol / g of thermoplastic polyvinyl alcohol derivative, preferably equal to or higher than 0.03 mmol / g of thermoplastic polyvinyl alcohol derivative. The molar vinyl concentration b can be determined from a known amount of solid reaction product by first separating the carboxylic acid residue and the thermoplastic polyvinyl alcohol derivative into two separate phases by heptane extraction, thereby forming two separate samples. vin The vinyl content can then be determined from the two separate samples. Vinyl molar concentration of thermoplastic polyvinyl alcohol derivatives b vin The molar vinyl content of the carboxylic acid residues can be determined, for example, by dissolving the thermoplastic polyvinyl alcohol in water and using an iodine titration method in accordance with standard ISO 3961:2009 (E). For example, the molar vinyl content of the carboxylic acid residues can be determined using an iodine titration method or by gas chromatography from heptane according to standard ISO 3961:2009 (E). vin For example, a headspace GC-MDS device can be used for gas chromatography analysis, wherein substances can be detected by their specific retention time, ie the time required for a particular substance to flow through a separation column of the gas chromatography apparatus.
[0096] The carboxylic acid residue RD1; RD2; RD3 and / or the salt of the carboxylic acid residue may account for up to half of the amount of the added reagent RGT1. When the total weight of the reaction product PROD1 or the solid reaction product OBJ1 is determined, the amount of the carboxylic acid residue may be up to 5% by weight, or up to 3% by weight. Preferably, the salt of the carboxylic acid residue may be present in an amount equal to or less than 1% by weight, more preferably equal to or less than 0.5% by weight, and most preferably equal to or less than 0.1% by weight.
[0097] Method for making paper substrate suitable for bonding silicone in catalytic hydrosilation reaction and products thereof
[0098] See also Figure 3a , 3b, 4 and 5, a paper substrate SUBST1 suitable for bonding silicone SIL1 in a catalytic hydrosilation reaction can be obtained by providing a cellulose fiber-based support layer PAP1 and coating the cellulose fiber-based support layer PAP1 with a coating composition to form a primer layer PRIM1, thereby obtaining a paper substrate SUBST1, wherein the coating composition comprises a reaction product PROD1, wherein the reaction product PROD1 contains a thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3 and a carboxylic acid residue RD1; RD2; RD3. The cellulose fiber-based support layer PAP1 can alternatively be coated with a coating composition formed with a solid reaction product OBJ1, for example, by dissolving the solid reaction product OBJ1 in water AQUA1, thereby forming an aqueous solution PR1 containing a thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3 and a carboxylic acid residue RD1.
[0099] The coating composition containing the reaction product PROD1 or the aqueous solution PR1 containing the thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3 and the carboxylic acid residue RD1; RD2; RD3 can be coated on the cellulose fiber-based support layer PAP1 by conventional paper coating methods. The coating of the cellulose fiber-based support layer with the primer layer PRIM1 containing the thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3 and the carboxylic acid residue RD1; RD2; RD3 provides an unprecedented method for improving the release properties of a subsequent release layer applied on top of the primer layer, especially when using fast-curing silicone compounds.
[0100] See also Figure 3a and 3b . The solid reaction product OBJ1 containing the thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3 and the carboxylic acid residue RD1; RD2; RD3 can be dissolved with water AQUA1 to form an aqueous solution PR1. The aqueous solution PR1 can be coated on at least one side of the cellulose fiber-based support layer PAP1 to form a paper substrate SUBST1 with a primer layer PRIM1, which contains the thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3, wherein the thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3 contains at least some ester-bonded side chains with vinyl ends, wherein the side chains with vinyl ends contain a chain carbon structure of at least 4 carbon atoms; the primer layer PRIM1 also contains the carboxylic acid residue RD1; RD2; RD3.
[0101] If necessary, an alkaline agent BASE1 (e.g. NaOH) can be added to the aqueous solution PR1 for neutralization, wherein at least some of the carboxylic acid residues RD1; RD2; RD3 react with at least the alkaline agent BASE1, thereby forming the corresponding carboxylate salts. The aqueous solution PR1 can then be applied to a cellulose fiber-based support layer PAP1 to form a paper substrate SUBST1.
[0102] Paper substrate
[0103] See also Figure 4 and Figure 5 . The paper substrate SUBST1 used in this article is a paper suitable for use as a release liner. Paper suitable for use as a release liner refers to a finished cellulose fiber-based support layer manufactured on a papermaking machine and coated with a primer layer. The finishing of the cellulose fiber-based support layer PAP1 can be carried out by surface sizing and calendering. Surface sizing and calendering improve the smoothness of the paper surface. Surface sizing refers to a sizing layer that can be applied on the surface of the cellulose fiber-based support layer PAP1. Surface sizing and calendering can also be used to reduce the thickness of the paper and reduce the porosity of the paper surface. The calendering process can be performed on the formed paper substrate SUBST1 before or after applying the primer layer. The calendering process may include the use of a calender, a multi-clip calender and / or a super calender to modify the surface properties of the paper and / or to bring the paper to a final thickness. In the manufacture of release liners, the quality of paper and suitability for coating with a silicone polymer-based compound (i.e., a release coating) can be determined based on the smoothness, density, porosity, and transparency of the paper. The Bekk method can be used to determine the smoothness and / or porosity of paper for release liners. For the Bekk method, the ISO 5627 standard can be used. The air permeability of paper can be determined using the Gurley method. For the Gurley method, the ISO 5636-5:2013 standard can be used.
[0104] Other properties of paper generally suitable for release liner are smoothness of at least 900 seconds / minute (ISO5627), density of at least 1.0, for example 1.0 to 1.2, wherein density refers to grams per unit thickness (ISO 534) (ISO 536), porosity equal to or less than 15000 pm / Pas (ISO 11004), when the paper grammage is less than 70 g / m 2 When the transparency is equal to or higher than 40%, preferably equal to or higher than 44%, or when the paper weight is equal to or higher than 70g / m 2When the transparency is equal to or higher than 28%, preferably equal to or higher than 33% (ISO 2470), the parameter values correspond to the ISO standards cited in brackets. In practice, the types of paper used for release liner applications are vegetable parchment, greaseproof paper, coated paper and glassine paper. Among these, glassine paper is preferred for the industrial production of high-quality release liners due to the mechanical properties of the paper obtained in the manufacturing process.
[0105] Vegetable parchment is paper made from unsized waterleaf sheet (uncut paper, made from chemical wood pulp) that is typically treated in a bath of sulfuric acid. The treated paper is washed thoroughly to remove the acid and then dried. This chemical treatment creates a very flexible, stiff paper that is similar in appearance to real parchment. However, paper treated in this way has a tendency to become brittle and wrinkle after drying.
[0106] Therefore, vegetable parchment is often treated with a plasticizer such as glycerol or glucose.
[0107] Coated paper includes various papers that usually have a coating applied to the surface of the paper and then calendered to improve the surface properties of the product. Coated paper can be used as a release liner, which is a coated paper that is typically wood-free and made from chemical pulp such as kraft pulp. 5-12 g / m 2 Coating weight per side. The coating layer typically comprises a pigment (eg calcium carbonate and / or kaolin) and a binder (eg starch, polyvinyl alcohol and / or latex).
[0108] Glass paper is widely used in release liners for self-adhesive materials. Glass paper is usually made of bleached chemical pulp with a grammage range of 30 to 160 g / m 2 The glass paper used to make the release liner is coated with a primer layer, which is compatible with the release coating based on silicone polymer. The primer layer uses 1 to 10 g / m 2 The coating amount on each side is usually 2 to 5 g / m 2The coating amount on each side. The mixture for forming the primer layer for glass paper may contain water-soluble binders such as starch, polyvinyl alcohol and / or carboxymethyl cellulose. When producing glass paper, the pulp is refined to obtain fiber fineness, which can obtain a dense, nearly non-porous paper surface. Such a surface is resistant to air and liquids such as oil and water. When making glass paper, the pulp slurry is first refined to a high level, then the formed paper web is pressed and dried, and a primer layer coating is applied on the paper web surface. Before or after applying the primer layer, the glass paper is calendered with a multi-nip calender or a super calender to obtain a product with a high-density surface, high impact strength, high tear resistance and transparency. However, glass paper has a dimensional stability lower than that of conventional coated paper. Therefore, when making glass paper, the shrinkage of the formed fiber web is higher than that of conventional coated paper.
[0109] The grammage of greaseproof paper is similar to that of glassine paper. The main difference between greaseproof paper and glassine paper is the calendering treatment. While glassine paper is usually treated with supercalendering, greaseproof paper is not. Therefore, the tear resistance of greaseproof paper is reduced when compared to glassine paper.
[0110] See also Figure 5 , the paper substrate SUBST1 is used as a platform for a subsequent release coating, which is usually a silicone-based composition, which is applied in the form of oil on the paper substrate SUBST1, and then the release coating is cured to form a release layer SIL1. Thereafter, a product such as a self-adhesive label can be manufactured by coating the formed release layer SIL1 of the release liner REL1 with an adhesive to form an adhesive layer ADH1, and then adjoining a surface material FACE1 serving as a printable surface on the surface of the adhesive layer ADH1 to form a label laminate web FILM1.
[0111] The primer layer PRIM1 herein refers to a polymer-containing layer coated on the cellulose fiber-based support layer PAP1. The cellulose fiber-based support layer PAP1 may include one or more layers of primer layer PRIM1. When manufacturing the paper substrate SUBST1, the primer layer PRIM1 may be applied as a coating composition on the surface of the cellulose fiber-based support layer PAP1. The reaction product PROD1 may be applied to the cellulose fiber-based support layer PAP1 as an aqueous solution PR1 formed from a solid reaction product OBJ1. When the primer layer PRIM1 includes the reaction product PROD1, the primer layer PRIM1 may be used to increase the bonding strength between the paper substrate SUBST1 and the release layer SIL1 and / or optimize the release value of the release layer. The primer layer PRIM1 containing the reaction product PROD1 may be particularly useful for firmly anchoring the release layer to the paper substrate SUBST1, so that the release liner REL1 may be used as a reliable debonding platform in high-speed applications.
[0112] When the primer layer PRIM1 contains the reaction product PROD1, the ratio of the amount of vinyl in the carboxylic acid residues RD1; RD2; RD3 to the amount of vinyl in the thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3 can be determined. This ratio can range from 0.2 to 1. This ratio can be determined from a sample of the primer layer PRIM1 by first dissolving the sample in distilled water and then separating the carboxylic acid residues RD1; RD2; RD3 and the thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3 into two separate phases by heptane extraction, thereby forming a first phase containing the carboxylic acid residues RD1; RD2; RD3 dissolved in heptane and a second phase containing the thermoplastic polyvinyl alcohol derivative dissolved in distilled water. Then, the amount of vinyl can be determined separately from each of the two samples in the separate phases. The amount of vinyl in the carboxylic acid residue can be determined by gas chromatography after evaporation of the heptane. The amount of vinyl of the thermoplastic polyvinyl alcohol derivative in water can be determined by iodine titration according to standard ISO 3961:2009 (E).
[0113] The primer layer PRIM1 of the paper substrate SUBST1 containing the reaction product PROD1 contains a thermoplastic polyvinyl alcohol derivative PVA1 having a degree of hydrolysis of 60 mol % to 90 mol %. The thermoplastic polyvinyl alcohol derivative PVA1 thus promotes the hydrophilicity of the primer layer PRIM1. However, the carboxylic acid residue RD1; RD2; RD3 portion tends to be less water soluble and has a more hydrophobic nature. This is particularly true when the carboxylic acid residue RD1; RD2; RD3 is based on a fatty acid. Therefore, when applied to the primer layer together with the thermoplastic polyvinyl alcohol derivative PVA1, the carboxylic acid residue RD1; RD2; RD3 can be used as a surfactant. Therefore, the carboxylic acid residue RD1; RD2; RD3 can be configured to reduce the surface area of the primer layer PRIM1 exposed to water. Once present in the primer layer, the carboxylic acid residue RD1; RD2; RD3 can be further configured to reduce the entropy of the primer layer surface.
[0114] Because the carboxylic acid RD1; RD2; RD3 is not covalently bonded to the thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3, the carboxylic acid RD1; RD2; RD3 has a greater freedom of movement in a direction parallel to the surface plane of the primer layer PRIM1, which can improve the flow characteristics of the silicone-based release coating SIL1 when applied on the primer layer. Therefore, a more uniformly spread silicone-based release coating SIL1 can be obtained on the primer layer PRIM1. In other words, the silicone-based release coating SIL1 can be more evenly distributed on the primer layer PRIM1.
[0115] Therefore, the coating composition containing the reaction product PROD1, the aqueous solution PR1, or the solid reaction product OBJ1 can form a paper substrate SUBST1 having a primer layer PRIM1, wherein the primer layer PRIM1 contains a thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3, wherein the thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3 contains at least some ester-bonded side chains with a vinyl terminal, wherein the side chain with a vinyl terminal contains a chain carbon structure of at least 4 carbon atoms. Therefore, the thermoplastic polyvinyl alcohol derivative can improve the anchoring of the subsequent silicone-based release coating SIL1. The carboxylic acid residue RD1; RD2; RD3 is also present in the reaction product PROD1, the aqueous solution PR1 or the solid reaction product OBJ1, which has the effect of further improving the flow characteristics of the silicone-based release coating SIL1.
[0116] Therefore, the primer layer PRIM1 formed by the reaction product PROD1, the aqueous solution PR1 or the solid reaction product OBJ1 can make the thermoplastic polyvinyl alcohol derivative CMP1; CMP2; CMP3 uniformly distributed on the surface and improve the surface properties of the paper substrate SUBST1. Therefore, the vinyl carboxylic acid residue RD1; RD2; RD3 obtainable by the ester bond forming condensation reaction between the organic acid anhydride AH1; AH2; AH3; AH4; AH5 and the thermoplastic polyvinyl alcohol PVA1 having a hydroxyl group can be used as a surfactant on the paper substrate SUBST1.
[0117] Experimental Examples and Comparative Examples
[0118] Comparative Examples C1 to C3 and Examples E1 and E2 are given below. Examples E1 and E2 demonstrate how some aspects of the invention may be implemented in practice.
[0119] Example E1 - Melt State Reaction of Polyvinyl Alcohol and Acetyl Undecylenic Anhydride
[0120] An experimental study was conducted in which a mixture containing thermoplastic polyvinyl alcohol and acetyl undecylenic anhydride was set to react in an ester bond forming condensation reaction in a molten state to obtain a reaction product containing a thermoplastic polyvinyl alcohol derivative and a carboxylic acid residue. Acetyl undecylenic anhydride is an asymmetric anhydride, which contains an acyl group that can be derived from 10-undecylenic acid and has a vinyl group at the end; the other acyl group can be derived from acetic acid. Therefore, acetyl undecylenic anhydride has a chain having a chain carbon structure and a vinyl group at the end. The amount of acetyl undecylenic anhydride mixed with the thermoplastic polyvinyl alcohol was determined to be 5% by weight based on the total weight of the mixture. The reaction was carried out in a conical twin-screw extruder ( The extruder is operated on a 100 mm (600 ft) extruder (1000 ft) with a counter-rotating screw diameter of 32 mm and a screw length of 330.7 mm), the extruder comprising a feed unit, three heating zones and a die section for extruding the material.
[0121] In the experimental study, 1.9 kg of thermoplastic polyvinyl alcohol (Kuraray The extruder is then fed with 0.1 kg of acetyl undecylenic anhydride through a feed unit. A screw speed of 30 rpm is used to mix the mixture. The three heating zones are adjusted to have a non-decreasing temperature profile, thereby providing a smooth operating performance. The temperature of the first heating zone adjacent to the feed unit is 190 ° C, the temperature of the second heating zone is also 190 ° C, and the temperature of the third heating zone is 195 ° C. The die zone adjacent to the third heating zone is set to a temperature of 200 ° C. Therefore, a 5 ° C temperature increase is used between the second and third zones and between the third zone and the die zone. The temperature distribution and screw geometry are further selected so that the first zone has reached the melting point temperature of the mixture. With the selected screw speed and screw geometry, the reaction duration in the molten state is less than 5 minutes. Therefore, acetyl undecylenic anhydride undergoes an ester bond formation condensation reaction with thermoplastic polyvinyl alcohol in a molten state. The reaction product contains 10-undecenoic acid and acetic acid (as carboxylic acid residues), and a thermoplastic polyvinyl alcohol derivative containing ester-bonded 10-undecenoic acid groups. The reaction product is extruded through a die zone and air-cooled to reduce the temperature of the reaction product to below the melting point of the mixture and form a solid reaction product, i.e., an extrudate. The cured reaction product is pelletized using a thermoplastic pelletizer (CF SCHEER & CIE, Model D-7000 Stuttgart 3) after extrusion.
[0122] Example E2 - Melt State Reaction of Polyvinyl Alcohol and Undecylenic Anhydride
[0123] Experiment E2 is a repetition of Example E1, wherein 5 wt% of acetyl undecylenic anhydride has been replaced by the same amount of undecylenic anhydride. Undecylenic anhydride is a symmetrical anhydride comprising two identical acyl groups, which may be derived from 10-undecylenic acid. Therefore, undecylenic anhydride has two symmetrical chains, both of which have a chain-like carbon structure with a vinyl end.
[0124] When undecylenic anhydride is subjected to an ester bond-forming condensation reaction with thermoplastic polyvinyl alcohol in a molten state, the reaction product contains only 10-undecylenic acid as a carboxylic acid residue in addition to the thermoplastic polyvinyl alcohol derivative containing an ester-bonded 10-undecylenic acid group.
[0125] Comparative Example C1:
[0126] Comparative Example C1 is a repetition of Example E1, wherein 5 wt% of acetyl undecenoic anhydride has been replaced by the same amount of 10-undecenoic acid. 10-Undecenoic acid is a carboxylic acid having a chain carbon structure with a vinyl group at the end.
[0127] When 10-undecenoic acid was used, no ester bond-forming condensation reaction with thermoplastic polyvinyl alcohol in a molten state was observed. The reaction product did not contain a thermoplastic polyvinyl alcohol derivative having covalently bonded side chains at least some of which were terminated with vinyl groups.
[0128] Comparative Example C2:
[0129] Comparative Example C2 is a repetition of Example E1, wherein 5% by weight of acetyl undecylenic anhydride has been replaced by the same amount of ethyl undecylenate. Ethyl undecylenate is the ethyl ester of 10-undecylenic acid. In addition, 0.5% by weight of tin ethylhexanoate is added as a catalyst.
[0130] When ethyl undecylenate is used, no ester bond-forming condensation reaction with thermoplastic polyvinyl alcohol in a molten state is observed. The reaction product does not contain a thermoplastic polyvinyl alcohol derivative having covalently bonded side chains at least some of which are terminated with vinyl groups.
[0131] Comparative Example C3:
[0132] Comparative Example C3 is a repetition of Example E1, wherein 5 wt % of acetyl undecylenic anhydride has been replaced by the same amount of 10-undecylenal. 10-undecylenal is an aldehyde that also contains vinyl. In addition, 5 wt % of acetic acid is added as a catalyst. The purpose of this comparative example is to evaluate the feasibility of acetalization under similar molten state conditions, as shown in Example E1.
[0133] When 10-undecenal was used, no condensation reaction with thermoplastic polyvinyl alcohol to form acetal bonds was observed in the molten state. The results of Comparative Example C3 indicate that acetalization in the molten state is not feasible under the reaction conditions studied. The reaction product does not contain a thermoplastic polyvinyl alcohol derivative having covalently bonded side chains with at least some side chain ends being vinyl, such as the anhydride-based esterification reaction in the molten state of Example E1.
[0134] A method for measuring the adhesion of silicone
[0135] Samples of each of the extruded reaction products prepared in Examples E1-E2 and Comparative Examples C1-C3 were dissolved in water at 10% solids. Unmodified polyvinyl alcohol ( 3-80 grade) was used as a reference sample, which can be used as a negative control to determine the effect of unmodified polyvinyl alcohol on the adhesion of silicone. Anchorage is a term used in the art to describe the connection of the release coating to the paper substrate. Anchorage can be measured as the relative peeling of the silicone from the paper substrate. A relative peeling value of 1 indicates perfect anchoring of the silicone, so that the release coating is completely anchored to the substrate. A relative peeling value of 2 or 3 means that the release coating is not fully attached to the paper substrate.
[0136] Glass paper (UPM Golden, 57 g / m 2 ), thereby obtaining a paper substrate with a primer layer comprising an unmodified commercial polyvinyl alcohol grade without vinyl, a modified commercial polyvinyl alcohol prepared using different reagents. The coating amount applied to each glass paper was 2 g / m 2 After coating, the paper substrate thus prepared was dried at 105° C. for 1 minute and conditioned at 23° C. and 50% RH (relative humidity) overnight before siliconization.
[0137] All paper substrates were subsequently siliconized, i.e., a silicone resin prepared from Wacker Dehesive SFX 251 and V58 crosslinker (all components provided by Wacker) was applied to the paper substrate using a C05 catalyst. The silicone resin applied to the paper substrate was prepared by stirring 87.44 parts / weight of debonding agent SFX 251 with 10.39 parts of V58 crosslinker for 2 minutes, then adding 2.17 parts of C05 platinum catalyst and stirring for 5 minutes. The silicone resin thus prepared was then applied on top of the paper substrate by a blade coater and cured at 105°C for 1 minute, thereby curing the silicone resin into a release layer and forming a release liner. Each paper substrate was coated with 1.2 g / m 2 of the silicone resin thus prepared. The silicone adhesion was tested immediately after the formed release liners were siliconized. This is referred to as the initial peel level. To further observe the combined effect of hot conditions and label adhesive on the silicone adhesion level over time, adhesive labels with water-based glue were attached to each formed release liner immediately after siliconization, and the laminates thus formed were stored at 50°C and 75% relative humidity for 2 days, 1 week, and 2 weeks before the silicone adhesion level was measured again.
[0138] The silicone adhesion level in each release liner sample was determined using a semi-automatic method, wherein the amount of silicone was measured using an x-ray fluorescence spectrometer (Oxford Lab-X-3000) before and after the release liner sample was stripped a limited number of times. The release liner sample was placed on top of the felt so that the siliconized surface of the release liner sample faced the felt. The peeling was performed by pressing the sample on the felt with a constant pressure and rotating the sample around its axis 10 times to improve the reliability and comparability of the results. In the case of 2 days, 1 week and 2 weeks of measurement, the release liner was tested after the label was removed from the laminate. Therefore, 2 days, 1 week and 2 weeks of measurement were performed on the surface in contact with the adhesive. For each sample, 3 parallel peeling measurements were performed and their arithmetic mean was calculated. The results of the peeling test are shown in Table 1 (as shown in the following table). A friction value of 1 represents the lowest acceptable level. An example of a device suitable for producing peeling on the release liner surface is a Satra friction tester, which has a rotating head that fixes a circular felt pad under a standard load, so that the wear resistance of the release layer can be semi-automatically tested.
[0139] Table 1. Silicone peeling results. The degree of peeling is expressed on a 1 to 3 scale: 1 = no peeling, 2 = visible peeling, 3 = significant or complete peeling.
[0140]
[0141] The test results show that primer layers containing thermoplastic polyvinyl alcohol derivatives of Example E1 or E2 (meaning thermoplastic polyvinyl alcohol derivatives obtainable by condensation reaction of polyvinyl alcohol and organic anhydrides in the molten state through ester bond formation) work well with modern fast-curing silicone systems. Release liner samples containing the reaction product of one of Examples E1 or E2 exhibit excellent relative release values, which remain consistent over time. This is not the case for the reference samples and samples containing the products of Comparative Examples C1-C3. In view of the test results, paper substrates containing thermoplastic polyvinyl alcohol derivatives of polyvinyl alcohol and organic anhydrides in the molten state through ester bond condensation reaction show excellent silicone adhesion levels when relative release is measured. This indicates better anchoring capabilities of the same silicone system.
[0142] Determination of carboxylic acid residues in thermoplastic polyvinyl alcohol derivatives by heptane extraction
[0143] Measurement principle
[0144] After the carboxylic acid residue and the thermoplastic polyvinyl alcohol derivative are first separated into two separate phases, for example, by dissolving a small amount of the solid reaction product in distilled water and performing a heptane extraction, the carboxylic acid residue can be extracted into the heptane phase, since heptane is a volatile organic solvent, and the presence of the carboxylic acid residue can be determined from the solid reaction product. After evaporation of the heptane, the carboxylic acid residue is silylated and analyzed by gas chromatography using a flame ionization detector. Silylation of the carboxylic acid residue improves the thermal stability and volatility of the compound for gas chromatography analysis.
[0145] Reagents and materials
[0146] Indicator: 0.1% bromocresol green in ethanol. Bromocresol green is a pH indicator that turns yellow when the pH is below 3.8 and blue when the pH is above 5.4.
[0147] Sulfuric acid, H2SO4 (0.05 mol / l).
[0148] Solvent: n-heptane.
[0149] - Standard solution (0.05 mg / ml); in heptane, heneicosanoic acid as internal standard.
[0150] • Silylating agents; bis-(trimethylsilyl)-trifluoroacetamide (BSTFA) and trimethylchlorosilane (TMCS).
[0151] Sample preparation
[0152] 10 g of a reaction product produced by a molten-state reaction of thermoplastic polyvinyl alcohol and an organic acid anhydride was dissolved in deionized water at a solid content of 10 wt % while stirring at 90° C. to form a sample for analysis. When a large amount of organic acid anhydride is used in the molten-state reaction, the sample may be further diluted with deionized water, for example, to a solid content of 1 to 10 wt %.
[0153] plan
[0154] 1. Use a pipette to transfer 5 ml of sample into a test tube with a screw cap.
[0155] 2. Add a few drops of indicator.
[0156] 3. Adjust the pH value of the sample to a value close to 3 with sulfuric acid, causing the sample color to change from blue-green to yellow.
[0157] 4. Add 1 ml of standard solution and 3 ml of n-heptane solvent to the test tube.
[0158] 5. Close the screw cap of the test tube and shake vigorously for 2 minutes.
[0159] 6. The tubes were centrifuged at 1400 rpm (Hermle Z513, speed 1000) for 5 minutes to obtain two phases: an aqueous phase containing the thermoplastic polyvinyl alcohol derivative and an organic solvent (n-heptane) phase containing carboxylic acid residues on top of the aqueous phase.
[0160] 7. Carefully transfer the organic solvent (n-heptane) phase to an empty test tube using a pipette to collect the organic solvent (n-heptane) phase.
[0161] 8. If a thin emulsion layer forms at the interface of the two phases in the test tube, keep it for the re-extraction stage.
[0162] 9. Repeat the extraction (steps 4 to 8 above) with 3 ml of pure heptane and combine the extracts.
[0163] 10. If necessary, repeat the extraction (steps 4 to 8 above) again to collect all organic solvent (n-heptane) phases into a combined extract.
[0164] 11. Evaporate the organic solvent (n-heptane) in the combined extracts using dry nitrogen. During evaporation, place the sample tube in a warm water bath to facilitate evaporation of the organic solvent (n-heptane).
[0165] 13. To ensure that the organic solvent (n-heptane) is completely evaporated, the sample is placed in a vacuum drying oven at 40°C for 20 minutes to obtain a dry sample.
[0166] 14. Add 300 μl of silylating agent mixture to the dried sample (50 ml BSTFA and 25 ml TMCS).
[0167] 15. The dried sample was silylated at 70°C for 30 minutes.
[0168] 16. Analyze the samples in a gas chromatograph.
[0169] For example, gas chromatography analysis can be performed using a headspace GC-MDS instrument, wherein the silylated carboxylic acid can be detected by its specific retention time, ie the time it takes for the specific substance to flow through the separation column of the gas chromatography apparatus.
[0170] Determination of reaction product composition by NMR analysis
[0171] Alternatively or additionally, proton nuclear magnetic resonance ( 1 H-NMR) analysis can be used to determine the presence of functional groups based on the chemical shift values δ. After the carboxylic acid residue and the thermoplastic polyvinyl alcohol derivative are first separated into two separate phases, the presence of vinyl groups can be determined from each sample separately. 1The sample for H-NMR analysis is, for example, prepared by dissolving 1 to 10 mg of the carboxylic acid residue or the thermoplastic polyvinyl alcohol derivative in 1 ml of DMSO-d6 solvent and measuring the standard by scanning 16 times for each prepared NMR sample using a suitable analytical instrument (e.g., Bruker AVANCE series spectrometer (400 Hz)). 1 H spectrum. Typical signals for vinyl groups can be detected in the following region: δ = about 4.8 to 6.0 ppm. For example, quantification of 10-undecenoic acid can be performed using the peak at δ = 5.7 to 5.9 ppm. H The adjacent methine proton of (OH)-CH2) is located at δ = 3.8 to 3.9 ppm and can be used as a reference point. By calculating the relative peak area of one proton in the polyvinyl alcohol backbone and the vinyl group, the relative peak area of the proton in the vinyl group can be calculated using 1 H-NMR spectroscopy determines the mole fraction of vinyl per vinyl alcohol unit. In addition, when NMR samples prepared from solution before and after the ester bond formation melt state reaction are collected and analyzed, the NMR results can be further used to determine the efficiency of the melt state reaction. The degree of substitution (DS) can be quantified by Equation 2.
[0172] Formula 2:
[0173] Wherein, A1 represents the peak area of a vinyl proton, and A2 represents the peak area of a backbone proton.
[0174] Method for determining vinyl content in samples by iodine titration
[0175] Iodometric titration herein refers to a method based on the Wijs method according to standard ISO 3961:2009 (E), in which a known excess of iodine monochloride is added to a sample, which results in a reaction between the iodine monochloride and any double bonds present in the sample. The amount of iodine monochloride that reacts with the double bonds present in the sample is determined by reacting the remaining iodine monochloride with a known excess of potassium iodide to form iodine, and then titrating the stoichiometric amount with a sodium thiosulfate solution of known concentration. Thus, the iodine value of the sample is obtained, which specifies the amount of iodine (in grams) that can be formally added to the double bonds in a known amount of sample, and thus determines the number of double bonds in the sample. Vinyl is a double bond, so polyvinyl alcohol does not contain double bonds. Therefore, iodometric titration is a specific method that can be used to investigate the amount of vinyl present in a polyvinyl alcohol derivative sample and determine the vinyl molar concentration of the sample.
[0176] The iodine titration method based on the Wijs method can be used to measure the total number of vinyl double bonds in a sample dissolved in water or an organic solvent (such as n-heptane). Therefore, the total number of vinyl double bonds present in the molten state reaction product produced in the ester bond forming condensation reaction of the thermoplastic polyvinyl alcohol with hydroxyl groups and the organic acid anhydride containing the chain with a vinyl terminal can be determined separately from the carboxylic acid residue and the thermoplastic polyvinyl alcohol derivative, and once the reaction product is processed into two separate phases by heptane extraction, two separate samples are made, one sample containing the carboxylic acid residue is in an organic solvent (being n-heptane), and the other sample containing the thermoplastic polyvinyl alcohol derivative is in an aqueous phase. However, due to phase differences, the comparative analysis of the two iodine titration results may not be accurate enough.
[0177] The method disclosed below relates to determining the amount of vinyl groups from a sample containing only a polyvinyl alcohol derivative. The polyvinyl alcohol derivative has at least some ester-bonded side chains having vinyl groups at the end thereof due to an ester-bond-forming condensation reaction.
[0178] The iodometric titration method is based on the measured volume of iodine monochloride in acetic acid (Wijs solution), which can be added to a reaction solution containing a polyvinyl alcohol derivative, wherein the iodine monochloride reacts with the double bonds of the vinyl groups present in the polyvinyl alcohol derivative according to formula 3 (below), resulting in an electrophilic addition reaction that produces a dihalogenated single bond (one of the carbons is bonded to the iodine atom).
[0179] Formula 3:
[0180] Iodine monochloride is a photosensitive reagent and needs to be stored and incubated in the dark. After incubation in the dark for 1 hour, the amount of iodine that has reacted in the electrophilic addition reaction is determined by adding a measured volume of potassium iodide solution (15%, weight / volume) to the reaction solution, resulting in the remaining unreacted iodine chloride in the reaction solution forming molecular iodine according to Formula 4 (below).
[0181] Formula 4: ICl+KI→KCl+I2
[0182] The released molecular iodine is then titrated with a 0.1 N sodium thiosulfate standard solution, from which the stoichiometric amount of molecular iodine can be calculated according to Formula 5 (below).
[0183] Formula 5: I2+2Na2S2O3→2 NaI+Na2S2O4
[0184] Thus, the iodine titration method is capable of determining the iodine value, which is the amount of iodine (in grams) that has reacted with the functional vinyl groups in a known amount of the polyvinyl alcohol derivative, as shown in Formula 6 (below).
[0185] Formula 6:
[0186] Wherein, A is the thiosulfate consumption of the test sample (polyvinyl alcohol derivative containing functional vinyl groups) in milliliters, B is the thiosulfate consumption of a blank sample containing only the measured volume of iodine monochloride in acetic acid and the measured volume of potassium iodide solution, N is the normality of the thiosulfate solution in mol / l, and m is the mass of the test sample (polyvinyl alcohol derivative containing functional vinyl groups) in grams. When comparing the iodine values of multiple samples of polyvinyl alcohol derivative containing functional vinyl groups using iodometric titration, a sample containing only polyvinyl alcohol can be used as a blank sample. If the samples are obtained from different types of thermoplastic polyvinyl alcohols with different degrees of hydrolysis, a blank sample containing only polyvinyl alcohol can also be used.
[0187] Vinyl molar concentration b vin (mmol / g) can be determined according to Formula 7 (below), which is a simplified version of that obtained from Formula 6 (above):
[0188] Formula 7:
[0189] For example, when the thiosulfate consumption of 2.5 g of the test sample of the polyvinyl alcohol derivative containing a functional vinyl group in the iodine titration method is 46 ml, the thiosulfate consumption of the blank sample is 48 ml, the normality of the thiosulfate solution is 0.1 mol / l, and the vinyl molar concentration of the test sample is 0.08 mmol / g, it is determined as follows by using the formula of Formula 7:
[0190]
[0191] Provided below is an exemplary method for measuring the amount of vinyl groups in a dried thermoplastic polyvinyl alcohol derivative containing at least some ester-bonded side chains terminated with vinyl groups, wherein the thermoplastic polyvinyl alcohol derivative is obtained by a melt-state condensation reaction of thermoplastic polyvinyl alcohol with an organic acid anhydride having at least a chain having a chain-like carbon structure of at least 4 carbon atoms and terminated with a vinyl group.
[0192] The dried thermoplastic polyvinyl alcohol derivative can be obtained by heptane extraction and subsequent drying of the thermoplastic polyvinyl alcohol derivative from the reaction product as disclosed above with respect to the determination of carboxylic acid residues by gas chromatography analysis.
[0193] The amount of functional vinyl groups (i.e., vinyl molar concentration) can then be measured by iodometric titration, which comprises:
[0194] - adding a known mass of a dry polyvinyl alcohol derivative containing a functional vinyl group to distilled water to form a 10% (w / v) mixture, and stirring the mixture at ambient temperature or heating as required until a solution is obtained, thereby obtaining an aqueous solution containing the polyvinyl alcohol derivative containing a functional vinyl group;
[0195] - Collect a 25 ml aliquot of the aqueous solution containing the polyvinyl alcohol derivative containing a functional vinyl group into an empty flask
[0196] - add 25 ml of iodine chloride in acetic acid (Wijs solution) to the aliquot, thereby obtaining a test sample solution;
[0197] - Add 25 ml of iodine chloride in acetic acid (Wijs solution) to another flask containing 25 ml of distilled water to obtain a blank sample solution;
[0198] - The test sample solution and the blank sample solution were incubated in the dark for 1 hour;
[0199] - Add 15 ml of potassium iodide solution (15%, w / v) to each test sample solution and blank sample solution, and stir the solution thoroughly;
[0200] - Add starch as an indicator and titrate the test sample solution and the blank sample solution with 0.1N sodium thiosulfate;
[0201] - Calculating an iodine value which corresponds to the known mass of the dry polyvinyl alcohol derivative containing the functional vinyl groups and which is proportional to the amount of functional vinyl groups present in the dry polyvinyl alcohol derivative.
[0202] A starch indicator is added before titration to show the endpoint, which is observed as a dark blue or purple discoloration of the solution.
Claims
1. A method for producing a thermoplastic polyvinyl alcohol derivative, wherein the thermoplastic polyvinyl alcohol derivative comprises a side chain with a vinyl group at the end, the method comprising the following steps: - heating a thermoplastic polyvinyl alcohol having hydroxyl groups, wherein: Thermoplastic polyvinyl alcohol has been dried and has a degree of hydrolysis of 65 mol % to 90 mol %, and - mixing a reagent with thermoplastic polyvinyl alcohol, wherein the reagent is an organic anhydride having at least one chain having a linear carbon structure of at least 4 carbon atoms and terminating in a vinyl group, Thus, a mixture containing molten thermoplastic polyvinyl alcohol having hydroxyl groups and an organic acid anhydride containing a vinyl-terminated chain is obtained. - mixing the mixture at a temperature above the melting point of the mixture, thereby causing a reaction in the molten state, wherein at least some of the organic anhydride reacts with the hydroxyl groups of the thermoplastic polyvinyl alcohol in an ester bond forming condensation reaction, This results in the formation of a reaction product comprising: - carboxylic acid residues from an ester bond-forming condensation reaction, wherein at least some of said carboxylic acid residues contain vinyl-terminated chains, and - A thermoplastic polyvinyl alcohol derivative containing ester-bonded side chains, at least some of which are terminated with vinyl groups.
2. The method of claim 1, wherein: The temperature above the melting point of the mixture is 170°C to 210°C.
3. The method according to claim 1 or 2, wherein: The duration of the reaction in the molten state is less than 5 minutes.
4. The method according to claim 1 or 2, further comprising: - adding an inhibitor suitable for inhibiting spontaneous free-radical polymerization of vinyl groups; and / or - adding a catalyst suitable for catalyzing the condensation reaction forming the ester bond, The inhibitor and / or catalyst is added before or during mixing of the mixture.
5. The method according to claim 1 or 2, wherein: The amount of the agent is from 1% to 10% by weight when measuring the total weight of the mixture.
6. The method according to claim 1 or 2, wherein: The organic anhydride is aliphatic and is either a symmetrical anhydride or an asymmetrical anhydride.
7. The method according to claim 1 or 2, wherein: Organic anhydrides are anhydrides based on fatty acids.
8. The method of claim 7, wherein: The fatty acid-based anhydride comprises one acyl group or two acyl groups derived from 3-butenoic acid, 2,2'-dimethyl-4-pentenoic acid, 4-pentenoic acid, 7-octenoic acid, 8-nonenoic acid, 10-undecenoic acid or 12-tridecenoic acid.
9. The method according to claim 1 or 2, wherein: The organic anhydride is undecylenic anhydride, which is a symmetrical anhydride comprising two identical acyl groups derived from 10-undecylenic acid, each acyl group having a vinyl group at the end.
10. The method according to claim 1 or 2, wherein: The mixing is carried out in the reactor and / or the heating of the dried thermoplastic polyvinyl alcohol is carried out prior to the mixing.
11. The method according to claim 1 or 2, further comprising: - Extrusion; as well as - cooling the reaction product so that the temperature of the reaction product decreases and a solid reaction product is obtained; as well as - Shaping the solid reaction product into a compact form suitable for transport.
12. The method according to claim 1 or 2, further comprising: - removing at least part of the carboxylic acid residues from the reaction product during and / or after the condensation reaction, thereby obtaining a recyclable carboxylic acid residue.
13. The method of claim 12, further comprising: - Arranging at least some of the recyclable carboxylic acid residues to participate in a reaction to form a reagent for the recyclable carboxylic acid residues, in which reaction an organic anhydride is formed having at least one chain having a linear carbon structure of at least 4 carbon atoms and terminating in a vinyl group.
14. The method according to claim 1 or 2, further comprising: - using a basic agent to neutralize at least some of the carboxylic acid residues in the reaction product, thereby forming a salt of the carboxylic acid residues.
15. A solid reaction product prepared by the method of claim 11, comprising a thermoplastic polyvinyl alcohol derivative comprising at least some ester-bonded side chains terminated with vinyl groups, wherein: The side chain with a vinyl end contains a chain carbon structure of at least 4 carbon atoms, and the solid reaction product also contains a carboxylic acid residue, wherein the carboxylic acid residue is an organic compound, and the organic compound contains a chain carbon structure with at least 4 carbon atoms with a vinyl end of the same type as the side chain of the thermoplastic polyvinyl alcohol derivative, and the melting point of the reaction product is 170°C to 210°C.
16. The solid reaction product of claim 15, wherein: The amount of the thermoplastic polyvinyl alcohol derivative in the solid reaction product is 80% to 99.9% by weight of the solid reaction product.
17. The solid reaction product of claim 15 or 16, wherein: At least some of the carboxylic acid residues are in the form of carboxylate salts.
18. The solid reaction product comprising a thermoplastic polyvinyl alcohol derivative according to claim 15 or 16, wherein: The thermoplastic polyvinyl alcohol derivative has the following properties: - a degree of hydrolysis of 65 mol % to 90 mol %; and / or - When measured from a known amount of the solid reaction product by the following procedure, the molar concentration of vinyl groups b vin Equal to or higher than 0.01 mmol / g of thermoplastic polyvinyl alcohol derivative: firstly separating the carboxylic acid residue and the thermoplastic polyvinyl alcohol derivative into two separate phases by heptane extraction, thereby forming two separate samples, and then determining the amount of vinyl in the phase containing the thermoplastic polyvinyl alcohol derivative by iodine titration according to standard ISO 3961:2009 (E); and / or - Melt flow index is 0.5-300 g / 10 min when measured using standard ISO 1133, 210°C, 2.16 kg.
19. The solid reaction product comprising a thermoplastic polyvinyl alcohol derivative according to claim 15 or 16, wherein: Chain carbon structures contain 5 or more carbon atoms.
20. The solid reaction product comprising a thermoplastic polyvinyl alcohol derivative according to claim 15 or 16, wherein: The thermoplastic polyvinyl alcohol derivative is water-soluble and a solution can be obtained within 24 hours after mixing the solid reaction product with deionized water in a ratio of at least 1:10 weight / weight while continuously stirring at a temperature ranging from 40°C to 80°C, in which the thermoplastic polyvinyl alcohol derivative is dissolved.
21. A paper substrate suitable for bonding silicone in a catalytic hydrosilation reaction, the paper substrate comprising: - a cellulose fiber-based support layer; and A primer layer comprising a reaction product obtained by the process according to claim 1 or 2.
22. A paper substrate suitable for bonding silicone in a catalytic hydrosilation reaction, the paper substrate comprising: - a cellulose fiber-based support layer; and - a primer layer containing a thermoplastic polyvinyl alcohol derivative containing at least some ester-bonded side chains terminated with vinyl groups, Wherein, the ester-bonded side chain with a vinyl end contains a chain carbon structure of at least 4 carbon atoms, the primer layer also contains a carboxylic acid residue and / or a salt of the carboxylic acid residue, and the carboxylic acid residue and / or the salt of the carboxylic acid residue is an organic compound containing a chain carbon structure of at least 4 carbon atoms with a vinyl end of the same type as the ester-bonded side chain.
23. The paper substrate according to claim 21 or 22, wherein The paper substrate has the following properties: - a smoothness of at least 900 sec / min, determined in accordance with ISO 5627, and / or - a density of at least 1.0, wherein density is the number of grams per unit thickness, the thickness being determined in accordance with ISO 534 and the number of grams being determined in accordance with ISO 536, and / or - a porosity equal to or less than 15000 pm / Pas, determined according to ISO 11004, and / or - When the paper weight is less than 70g / m 2 When the transparency is equal to or higher than 40%, it is determined according to ISO 2470.
24. The paper substrate according to claim 21 or 22, wherein The cellulose fiber-based support layer is a calendered commercially produced paper substrate.
25. A method of making a paper substrate suitable for bonding silicone in a catalytic hydrosilation reaction, the method comprising the steps of: - heating a thermoplastic polyvinyl alcohol having hydroxyl groups, wherein: Thermoplastic polyvinyl alcohol has been dried and has a degree of hydrolysis of 65 mol % to 90 mol %, and - mixing a reagent with thermoplastic polyvinyl alcohol, wherein the reagent is an organic acid anhydride, the organic acid anhydride has at least one chain, the chain has a chain carbon structure of at least 4 carbon atoms and ends with a vinyl group, thereby obtaining a mixture containing molten thermoplastic polyvinyl alcohol having hydroxyl groups and an organic anhydride containing a chain terminated by a vinyl group, and - subjecting the mixture to mixing at a temperature above the melting point of the mixture, thereby causing a reaction in a molten state, wherein at least some of the organic anhydride reacts with the hydroxyl groups of the thermoplastic polyvinyl alcohol in an ester bond forming condensation reaction, This results in the formation of a reaction product comprising: o carboxylic acid residues from an ester-forming condensation reaction, wherein at least some of the carboxylic acid residues contain vinyl-terminated chains, and o a thermoplastic polyvinyl alcohol derivative containing ester-bonded side chains, at least some of which are terminated with vinyl groups, and - coating at least one side of the cellulose fiber-based support layer with a coating composition comprising the reaction product, Thus, a paper substrate with a primer layer is formed, the paper substrate comprising a thermoplastic polyvinyl alcohol derivative, the thermoplastic polyvinyl alcohol derivative comprising at least some ester-bonded side chains terminated by vinyl groups, wherein the side chains terminated by vinyl groups comprise a chain-like carbon structure of at least 4 carbon atoms, and the primer layer further comprises a carboxylic acid residue, wherein the carboxylic acid residue is an organic compound comprising a chain-like carbon structure of at least 4 carbon atoms terminated by vinyl groups of the same type as the side chains of the thermoplastic polyvinyl alcohol derivative, and the paper substrate is thus suitable for bonding silicone in a catalytic hydrosilation reaction.
26. The method of claim 25, further comprising: - before coating the cellulose fiber-based support layer, neutralizing at least some of the carboxylic acid residues of the reaction product with an alkaline agent to form a salt of the carboxylic acid residue, so that at least some of the carboxylic acid residues on the primer layer are in the form of a salt of said carboxylic acid residue.
Citation Information
Patent Citations
Cellulose fibre-based support intended to be siliconized
WO2005071161A1
A release liner composition, a base material and a method of producing a base material, and a surface treating agent for a base material and a use of a surface treating agent
WO2009147283A1
Cellulose fibre - based support containing a modified PVA layer, and a method its production and use
WO2011104427A1
Poly(vinyl alcohol) composition comprising polyol
CN101230176A
Fibre-based support containing a layer of a functionalized water-soluble polymer, method of production and use thereof
CN103890267A
